Salt form and crystal form of benzazepine fused ring compound and application of salt form and crystal form

CN119604507AActive Publication Date: 2025-03-11SHANGHAI JEMINCARE PHARMACEUTICALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380056745.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-05
Filing Date
2023-09-01
Publication Date
2025-03-11
Estimated Expiration
2043-09-01

AI Technical Summary

Technical Problem

Existing arginine vasopressin V2 receptor antagonists such as tolvaptan are metabolized in the body to produce drug-induced hepatotoxicity, which limits their application, and cannot effectively inhibit the binding of AVP to the receptor, resulting in limited therapeutic effects.

Method used

A new benzazepine compound, including maleate, fumarate, hydrochloride, sulfate, succinate, glycolate and other crystal forms, was developed and characterized by X-ray powder diffraction patterns Diffraction peak analysis ensures the stability and crystal-free structure of the compound, reduces the generation of metabolites, and improves the safety and therapeutic effect of the drug.

Benefits of technology

By preparing benzazepine compounds of different acid acid forms, we have achieved effective antagonism of AVP V2 receptors, reduced the risk of hepatotoxicity, improved the safety and therapeutic effect of the drug, and avoided drug-induced hepatotoxicity. question.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604507A_ABST
    Figure CN119604507A_ABST
Patent Text Reader

Abstract

The invention relates to a salt form, a crystal form and application of a benzazepine fused ring compound, in particular to maleate of a compound shown in a formula (I), and the structure of the maleate is shown in a formula (II). # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Benzazepine cyclopentane compound salt form, crystal form and application thereof

[0001] The present invention claims the following priority:

[0002] Application number CN 202211080826.4, application date September 5, 2022. Technical Field

[0003] The present invention belongs to the field of medicinal chemistry, and in particular, relates to a benzazepine cyclopentane compound salt form, a crystal form and applications thereof. Background Art

[0004] Hormones play a crucial role in regulating human internal homeostasis, with arginine vasopressin (AVP) being closely linked to the regulation of water and sodium metabolism. Disturbances in arginine vasopressin (AVP) metabolism can cause a variety of conditions, including hyponatremia, syndrome of inappropriate antidiuretic hormone secretion, congestive heart failure, cirrhosis, kidney disease, hypertension, and edema. Arginine vasopressin (AVP) receptor antagonists inhibit the binding of AVP to the receptor, thereby providing therapeutic benefits for these conditions. Arginine vasopressin V2 receptor antagonists, such as tolvaptan, can increase free water excretion without affecting electrolyte metabolism, making them ideal agents for treating these conditions. However, marketed AVP V2 receptor antagonists, such as tolvaptan, are metabolized by hepatic enzymes, producing a large number of metabolites in the body and leading to severe drug-induced hepatotoxicity. The FDA has issued a black box warning on the drug's label, restricting its use.

[0005] The patent application with application number PCT / CN2022 / 079350 and application date of March 4, 2022 provides a new AVP V2 receptor antagonist with the following structure:

[0006] Summary of the Invention

[0007] In one aspect of the present invention, the present invention provides a maleate salt of the compound represented by formula (I), the structure of which is shown in formula (II),

[0008] In another aspect of the present invention, the present invention provides a maleate salt of the compound represented by formula (I) (i.e., the compound represented by formula (II)) crystalline form A, and the X-ray powder diffraction pattern of crystalline form A has characteristic diffraction peaks at the following 2θ angles: 9.14±0.2°, 12.88±0.2°, 18.31±0.2°, 18.90±0.2°, 20.60±0.2°, and 27.61±0.2°.

[0009] In some embodiments of the present invention, the X-ray powder diffraction pattern of Form A has characteristic diffraction peaks at the following 2θ angles: 9.14±0.2°, 12.88±0.2°, 17.19±0.2°, 18.31±0.2°, 18.90±0.2°, 20.60±0.2°, 21.45±0.2°, and 27.61±0.2°.

[0010] In some embodiments of the present invention, the X-ray powder diffraction pattern of Form A has characteristic diffraction peaks at the following 2θ angles: 9.14±0.2°, 12.88±0.2°, 17.19±0.2°, 18.31±0.2°, 18.90±0.2°, 19.70±0.2°, 20.20±0.2°, 20.60±0.2°, 21.45±0.2°, 21.91±0.2°, and 27.61±0.2°.

[0011] In some embodiments of the present invention, the X-ray powder diffraction pattern of Form A has characteristic diffraction peaks at the following 2θ angles: 9.14±0.2°, 12.88±0.2°, 17.19±0.2°, 18.31±0.2°, 18.90±0.2°, 19.70±0.2°, 20.20±0.2°, 20.60±0.2°, 21.45±0.2°, 21.91±0.2°, 25.96±0.2°, 26.53±0.2°, 27.61±0.2°, 29.22±0.2°, and 30.20±0.2°.

[0012] In some embodiments of the present invention, the X-ray powder diffraction pattern of Form A has an X-ray powder diffraction pattern substantially as shown in FIG1 .

[0013] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of Form A is shown in Table 1 below.

[0014] Table 1

[0015] In another aspect of the present invention, the present invention also provides a maleate salt of the compound represented by formula (I) (i.e., the compound represented by formula (II)) crystalline form B, wherein the X-ray powder diffraction pattern of the crystalline form B has characteristic diffraction peaks at the following 2θ angles: 8.97±0.2°, 15.73±0.2°, 18.31±0.2°, 20.15±0.2°, 21.12±0.2°, and 24.70±0.2°.

[0016] In some embodiments of the present invention, the X-ray powder diffraction pattern of Form B has characteristic diffraction peaks at the following 2θ angles: 7.40±0.2°, 8.97±0.2°, 10.11±0.2°, 13.94±0.2°, 15.73±0.2°, 18.31±0.2°, 19.02±0.2°, 20.15±0.2°, 21.12±0.2°, and 24.70±0.2°.

[0017] In some embodiments of the present invention, the X-ray powder diffraction pattern of Form B has an X-ray powder diffraction pattern substantially as shown in FIG6 .

[0018] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of Form B is shown in Table 2 below.

[0019] Table 2

[0020] In another aspect of the present invention, the present invention also discloses a fumarate salt of the compound represented by formula (I), the structure of which is represented by formula (III).

[0021] In another aspect of the present invention, the present invention also discloses a fumarate salt of the compound represented by formula (I) (i.e., the compound represented by formula (III)) crystalline form C, and the X-ray powder diffraction pattern of crystalline form C has characteristic diffraction peaks at the following 2θ angles: 12.77±0.2°, 14.44±0.2°, 20.00±0.2°, 20.64±0.2°, 21.33±0.2°, and 21.87±0.2°.

[0022] In some embodiments of the present invention, the X-ray powder diffraction pattern of Form C has characteristic diffraction peaks at the following 2θ angles: 12.77±0.2°, 13.17±0.2°, 14.44±0.2°, 17.18±0.2°, 20.00±0.2°, 20.64±0.2°, 21.33±0.2°, 21.87±0.2°, 23.43±0.2°, and 25.86±0.2°.

[0023] In some embodiments of the present invention, the X-ray powder diffraction pattern of Form C has an X-ray powder diffraction pattern substantially as shown in FIG. 9 .

[0024] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of Form C are shown in Table 3 below.

[0025] Table 3

[0026] In another aspect of the present invention, the present invention provides a hydrochloride salt of a compound represented by formula (I), the structure of which is represented by formula (IV).

[0027] In another aspect of the present invention, the present invention provides a hydrochloride salt of the compound represented by formula (I) (i.e., the compound represented by formula (IV)) form D, the X-ray powder diffraction pattern of the form D having characteristic diffraction peaks at the following 2θ angles: 8.13±0.2°, 9.27±0.2°, 9.91±0.2°, 13.53±0.2°, 16.37±0.2°, and 17.09±0.2°.

[0028] In some embodiments of the present invention, the X-ray powder diffraction pattern of Form D has characteristic diffraction peaks at the following 2θ angles: 8.13±0.2°, 9.27±0.2°, 9.91±0.2°, 12.86±0.2°, 13.53±0.2°, 16.37±0.2°, 17.09±0.2°, 18.67±0.2°, 21.77±0.2°, and 23.81±0.2°.

[0029] In some embodiments of the present invention, the X-ray powder diffraction pattern of Form D has an X-ray powder diffraction pattern substantially as shown in FIG. 12 .

[0030] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of Form D are shown in Table 4 below.

[0031] Table 4

[0032] In another aspect of the present invention, the present invention provides a hydrochloride salt of the compound represented by formula (I) (i.e., the compound represented by formula (IV)) in form E, wherein the X-ray powder diffraction pattern of the form E has characteristic diffraction peaks at the following 2θ angles: 3.86±0.2°, 13.60±0.2°, 14.19±0.2°, 18.06±0.2°, 20.50±0.2°, and 21.24±0.2°.

[0033] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form E has characteristic diffraction peaks at the following 2θ angles: 3.86±0.2°, 6.74±0.2°, 11.73±0.2°, 13.60±0.2°, 14.19±0.2°, 18.06±0.2°, 20.50±0.2°, 21.24±0.2°, 23.72±0.2°, and 24.06±0.2°.

[0034] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form E has an X-ray powder diffraction pattern substantially as shown in FIG15 .

[0035] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystalline form E is shown in Table 5 below.

[0036] Table 5

[0037] In another aspect of the present invention, the present invention also provides a hydrochloride salt of the compound represented by formula (I) (i.e., the compound represented by formula (IV)) form F, the X-ray powder diffraction pattern of the form F having characteristic diffraction peaks at the following 2θ angles: 5.84±0.2°, 11.77±0.2°, 13.29±0.2°, 17.82±0.2°, 20.49±0.2°, and 20.94±0.2°.

[0038] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form F has characteristic diffraction peaks at the following 2θ angles: 5.84±0.2°, 11.77±0.2°, 13.29±0.2°, 14.34±0.2°, 17.82±0.2°, 18.67±0.2°, 20.49±0.2°, 20.94±0.2°, 23.02±0.2°, and 23.68±0.2°.

[0039] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form F has an X-ray powder diffraction pattern substantially as shown in FIG18 .

[0040] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form F is shown in Table 6 below.

[0041] Table 6

[0042] In another aspect of the present invention, the present invention also provides a sulfate of the compound represented by formula (I), the structure of which is represented by formula (V).

[0043] In another aspect of the present invention, the present invention also provides a sulfate salt of the compound represented by formula (I) (i.e., the compound represented by formula (V)) crystal form G, the X-ray powder diffraction pattern of the crystal form G having characteristic diffraction peaks at the following 2θ angles: 10.30±0.2°, 13.02±0.2°, 16.60±0.2°, 18.53±0.2°, 20.67±0.2°, and 22.26±0.2°.

[0044] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form G has characteristic diffraction peaks at the following 2θ angles: 6.46±0.2°, 10.30±0.2°, 13.02±0.2°, 16.60±0.2°, 17.66±0.2°, 18.53±0.2°, 19.98±0.2°, 20.67±0.2°, 22.26±0.2°, and 23.62±0.2°.

[0045] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form G has an X-ray powder diffraction pattern substantially as shown in Figure 21.

[0046] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the sulfate crystal form G is shown in Table 7 below.

[0047] Table 7

[0048] In another aspect of the present invention, the present invention also provides a succinate salt of the compound represented by formula (I), the structure of which is shown in formula (VI),

[0049] In another aspect of the present invention, the present invention also provides a succinate salt of the compound represented by formula (I) (i.e., the compound represented by formula (VI)) crystal form H, the X-ray powder diffraction pattern of the crystal form H having characteristic diffraction peaks at the following 2θ angles: 10.30±0.2°, 14.63±0.2°, 18.59±0.2°, 20.13±0.2°, 21.83±0.2°, and 22.30±0.2°.

[0050] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form H has characteristic diffraction peaks at the following 2θ angles: 10.30±0.2°, 12.91±0.2°, 14.63±0.2°, 18.59±0.2°, 19.41±0.2°, 20.13±0.2°, 20.69±0.2°, 21.83±0.2°, 22.30±0.2°, and 23.65±0.2°.

[0051] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form H has an X-ray powder diffraction pattern substantially as shown in FIG. 24 .

[0052] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form H is shown in Table 8 below.

[0053] Table 8

[0054] In another aspect of the present invention, the present invention also provides a succinate salt crystal form J of the compound represented by formula (I) (i.e., the compound represented by formula (VI)), and the X-ray powder diffraction pattern of the crystal form J has characteristic diffraction peaks at the following 2θ angles: 9.61±0.2°, 11.56±0.2°, 12.93±0.2°, 17.12±0.2°, 17.71±0.2°, and 19.95±0.2°.

[0055] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form J has characteristic diffraction peaks at the following 2θ angles: 9.61±0.2°, 11.56±0.2°, 12.93±0.2°, 13.76±0.2°, 17.12±0.2°, 17.71±0.2°, 19.51±0.2°, 19.95±0.2°, 21.83±0.2°, and 22.42±0.2°.

[0056] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form J has an X-ray powder diffraction pattern substantially as shown in FIG. 27 .

[0057] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form J is shown in Table 9 below.

[0058] Table 9

[0059] In another aspect of the present invention, the present invention also provides a glycolate of the compound represented by formula (I), the structure of which is represented by formula (VII),

[0060] In another aspect of the present invention, the present invention also provides a crystalline form K of the glycolate salt of the compound represented by formula (I) (i.e., the compound represented by formula (VII)), wherein the X-ray powder diffraction pattern of the crystalline form K has characteristic diffraction peaks at the following 2θ angles: 12.51±0.2°, 15.99±0.2°, 18.71±0.2°, 20.18±0.2°, 20.59±0.2°, and 21.64±0.2°.

[0061] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form K has characteristic diffraction peaks at the following 2θ angles: 12.51±0.2°, 13.62±0.2°, 15.99±0.2°, 16.65±0.2°, 18.71±0.2°, 20.18±0.2°, 20.59±0.2°, 21.64±0.2°, 22.62±0.2°, and 24.53±0.2°.

[0062] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form K has an X-ray powder diffraction pattern substantially as shown in Figure 30.

[0063] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form K is shown in Table 10 below.

[0064] Table 10

[0065] In another aspect of the present invention, the present invention also provides a benzoate salt of the compound represented by formula (I), whose structure is shown in formula (VIII),

[0066] In another aspect of the present invention, the present invention also provides a benzoic acid cocrystal form L of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the form L has characteristic diffraction peaks at the following 2θ angles: 8.14±0.2°, 8.76±0.2°, 9.55±0.2°, 12.62±0.2°, 16.43±0.2°, and 18.05±0.2°.

[0067] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form L has characteristic diffraction peaks at the following 2θ angles: 8.14±0.2°, 8.76±0.2°, 9.55±0.2°, 12.62±0.2°, 16.43±0.2°, 17.68±0.2°, 18.05±0.2°, 18.95±0.2°, 19.32±0.2°, and 19.73±0.2°.

[0068] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form L has an X-ray powder diffraction pattern substantially as shown in Figure 33.

[0069] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form L is shown in Table 11 below.

[0070] Table 11

[0071] In another aspect of the present invention, the present invention also provides a benzoic acid cocrystal form M of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the form M has characteristic diffraction peaks at the following 2θ angles: 9.31±0.2°, 13.77±0.2°, 14.54±0.2°, 19.84±0.2°, 20.34±0.2°, and 21.70±0.2°.

[0072] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form M has characteristic diffraction peaks at the following 2θ angles: 9.31±0.2°, 13.77±0.2°, 14.54±0.2°, 16.55±0.2°, 17.66±0.2°, 18.68±0.2°, 19.84±0.2°, 20.34±0.2°, 21.70±0.2°, and 23.32±0.2°.

[0073] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form M has an X-ray powder diffraction pattern substantially as shown in Figure 36.

[0074] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form M is shown in Table 12 below.

[0075] Table 12

[0076] In another aspect of the present invention, the present invention also provides a crystalline form N of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form N has characteristic diffraction peaks at the following 2θ angles: 10.38±0.2°, 13.54±0.2°, 14.41±0.2°, 16.32±0.2°, 18.10±0.2°, and 19.05±0.2°.

[0077] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form N has characteristic diffraction peaks at the following 2θ angles: 10.38±0.2°, 13.54±0.2°, 14.41±0.2°, 15.90±0.2°, 16.32±0.2°, 18.10±0.2°, 19.05±0.2°, 22.14±0.2°, 22.91±0.2°, and 23.66±0.2°.

[0078] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form N has an X-ray powder diffraction pattern substantially as shown in Figure 39.

[0079] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form N is shown in Table 13 below.

[0080] Table 13

[0081] In another aspect of the present invention, the present invention also provides a crystalline form O of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form O has characteristic diffraction peaks at the following 2θ angles: 4.75±0.2°, 9.65±0.2°, 15.70±0.2°, 16.88±0.2°, 18.00±0.2°, and 18.97±0.2°.

[0082] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form O has characteristic diffraction peaks at the following 2θ angles: 4.75±0.2°, 9.65±0.2°, 15.70±0.2°, 16.88±0.2°, 18.00±0.2°, 18.97±0.2°, 19.89±0.2°, 21.86±0.2°, 22.67±0.2°, and 24.30±0.2°.

[0083] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form O has an X-ray powder diffraction pattern substantially as shown in Figure 42.

[0084] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form O is shown in Table 14 below.

[0085] Table 14

[0086] In another aspect of the present invention, the present invention also provides a crystalline form P of the compound represented by formula (I), the X-ray powder diffraction pattern of the crystalline form P having characteristic diffraction peaks at the following 2θ angles: 13.07±0.2°, 17.98±0.2°, 21.64±0.2°, 23.78±0.2°, 26.36±0.2°, and 33.13±0.2°.

[0087] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form P has an X-ray powder diffraction pattern substantially as shown in Figure 45.

[0088] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form P is shown in Table 15 below.

[0089] Table 15

[0090] In another aspect of the present invention, the present invention also proposes a crystalline form Q of the compound represented by formula (I), the X-ray powder diffraction pattern of the crystalline form Q having characteristic diffraction peaks at the following 2θ angles: 3.48±0.2°, 10.60±0.2°, 12.32±0.2°, 15.41±0.2°, 16.60±0.2°, and 17.09±0.2°.

[0091] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form Q has characteristic diffraction peaks at the following 2θ angles: 3.48±0.2°, 10.60±0.2°, 12.32±0.2°, 15.41±0.2°, 16.60±0.2°, 17.09±0.2°, 17.75±0.2°, 18.79±0.2°, 20.49±0.2°, and 21.40±0.2°.

[0092] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form Q has an X-ray powder diffraction pattern substantially as shown in Figure 48.

[0093] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form Q is shown in Table 16 below.

[0094] Table 16

[0095] In another aspect of the present invention, the present invention also provides a crystalline form R of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form R has characteristic diffraction peaks at the following 2θ angles: 6.70±0.2°, 13.30±0.2°, 18.15±0.2°, 21.39±0.2°, 22.97±0.2°, and 26.71±0.2°.

[0096] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form R has an X-ray powder diffraction pattern substantially as shown in Figure 50.

[0097] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form R is shown in Table 17 below.

[0098] Table 17

[0099] In another aspect of the present invention, the present invention also provides a crystalline form S of the compound represented by formula (I), the X-ray powder diffraction pattern of the crystalline form S having characteristic diffraction peaks at the following 2θ angles: 14.97±0.2°, 15.34±0.2°, 17.97±0.2°, 22.81±0.2°, 23.54±0.2°, and 24.69±0.2°.

[0100] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form S has an X-ray powder diffraction pattern substantially as shown in Figure 53.

[0101] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form S is shown in Table 18 below.

[0102] Table 18

[0103] In another aspect of the present invention, the present invention also provides a crystalline form T of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form T has characteristic diffraction peaks at the following 2θ angles: 15.84±0.2°, 17.03±0.2°, 17.60±0.2°, 20.01±0.2°, 22.22±0.2°, and 22.82±0.2°.

[0104] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form T has characteristic diffraction peaks at the following 2θ angles: 13.64±0.2°, 14.70±0.2°, 15.84±0.2°, 17.03±0.2°, 17.60±0.2°, 19.01±0.2°, 20.01±0.2°, 22.22±0.2°, 22.82±0.2°, and 24.45±0.2°.

[0105] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form T has an X-ray powder diffraction pattern substantially as shown in Figure 56.

[0106] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form T is shown in Table 19 below.

[0107] Table 19

[0108] In another aspect of the present invention, the present invention also provides a crystalline form U of the compound represented by formula (I), wherein the X-ray powder diffraction pattern of the crystalline form U has characteristic diffraction peaks at the following 2θ angles: 8.01±0.2°, 9.27±0.2°, 12.68±0.2°, 16.15±0.2°, 17.94±0.2°, and 19.31±0.2°.

[0109] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form U has characteristic diffraction peaks at the following 2θ angles: 8.01±0.2°, 9.27±0.2°, 12.68±0.2°, 16.15±0.2°, 17.94±0.2°, 19.31±0.2°, 22.16±0.2°, 22.82±0.2°, 23.80±0.2°, and 24.08±0.2°.

[0110] In some embodiments of the present invention, the X-ray powder diffraction pattern of the crystalline form U has an X-ray powder diffraction pattern substantially as shown in Figure 59.

[0111] In some embodiments of the present invention, the X-ray powder diffraction pattern analysis data of the crystal form U is shown in Table 20 below.

[0112] Table 20

[0113] Definition and Description

[0114] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as commonly understood by one of ordinary skill in the art to which this invention belongs. All patents and publications to which this invention pertains are incorporated herein by reference in their entirety. Although any methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention, the preferred methods, devices, and materials are described herein.

[0115] "API" or "free state" refers to the free base form of the compound represented by formula (I).

[0116] "Crystal form" or "crystalline form" refers to a solid having a highly regular chemical structure, including, but not limited to, single-component or multi-component crystals, and / or polymorphs, solvates, hydrates, inclusion compounds, co-crystals, salts, solvates of salts, and hydrates of salts of a compound. Crystalline forms of a substance can be obtained by a number of methods known in the art. Such methods include, but are not limited to, melt crystallization, melt cooling, solvent crystallization, crystallization in a confined space, for example, in a nanopore or capillary, crystallization on a surface or template, for example, on a polymer, crystallization in the presence of an additive such as a co-crystallizing countermolecule, desolvation, dehydration, rapid evaporation, rapid cooling, slow cooling, vapor diffusion, sublimation, reactive crystallization, antisolvent addition, grinding, and solvent drop grinding, etc.

[0117] "Amorphous" or "amorphous form" refers to a substance formed when the particles (molecules, atoms, ions) are arranged in a three-dimensional space without periodicity, characterized by a diffuse, unsharp X-ray powder diffraction pattern. Amorphous is a special physical form of solid matter, and its locally ordered structure suggests that it is inextricably linked to crystalline forms. Amorphous forms of substances can be obtained by a variety of methods known in the art. Such methods include, but are not limited to, quenching, antisolvent flocculation, ball milling, spray drying, freeze drying, wet granulation, and solid dispersion techniques.

[0118] "Solvent" refers to a substance (typically a liquid) that can completely or partially dissolve another substance (typically a solid). Solvents useful in the practice of the present invention include, but are not limited to, water, acetic acid, acetone, acetonitrile, benzene, chloroform, carbon tetrachloride, dichloromethane, dimethyl sulfoxide, 1,4-dioxane, ethanol, ethyl acetate, butanol, tert-butanol, N,N-dimethylacetamide, N,N-dimethylformamide, formamide, formic acid, heptane, hexane, isopropanol, methanol, methyl ethyl ketone, 1-methyl-2-pyrrolidone, mesitylene, nitromethane, polyethylene glycol, propanol, 2-acetone, pyridine, tetrahydrofuran, toluene, xylene, mixtures thereof, and the like.

[0119] "Anti-solvent" refers to a fluid that promotes precipitation of a product (or product precursor) from a solvent. The anti-solvent can include a cold gas, or a fluid that promotes precipitation by a chemical reaction, or a fluid that reduces the solubility of the product in the solvent; it can be the same liquid as the solvent but at a different temperature, or it can be a different liquid from the solvent.

[0120] "Solvate" refers to a crystal having a solvent on the surface, in the crystal lattice, or both on the surface and in the crystal lattice, wherein the solvent may be water, acetic acid, acetone, acetonitrile, benzene, chloroform, carbon tetrachloride, dichloromethane, dimethyl sulfoxide, 1,4-dioxane, ethanol, ethyl acetate, butanol, tert-butanol, N,N-dimethylacetamide, N,N-dimethylformamide, formamide, formic acid, heptane, hexane, isopropanol, methanol, methyl ethyl ketone, methylpyrrolidone, mesitylene, nitromethane, polyethylene glycol, propanol, 2-propanone, pyridine, tetrahydrofuran, toluene, xylene, and mixtures thereof. A specific example of a solvate is a hydrate, wherein the solvent on the surface, in the crystal lattice, or both on the surface and in the crystal lattice is water. A hydrate may or may not have other solvents other than water on the surface, in the crystal lattice, or both on the surface and in the crystal lattice of the substance.

[0121] Crystalline or amorphous forms can be identified by a variety of technical means, such as X-ray powder diffraction (XRPD), infrared absorption spectroscopy (IR), melting point method, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), nuclear magnetic resonance, Raman spectroscopy, X-ray single crystal diffraction, dissolution calorimetry, scanning electron microscopy (SEM), quantitative analysis, solubility and dissolution rate, etc.

[0122] X-ray powder diffraction (XRPD) can detect information such as changes in crystal form, crystallinity, and crystalline state, and is a common means of identifying crystal forms. The peak position of the XRPD pattern depends primarily on the structure of the crystal form and is relatively insensitive to experimental details, while its relative peak height depends on many factors related to sample preparation and instrument geometry. Therefore, in some embodiments, the crystal form of the present invention is characterized by an XRPD pattern with certain peak positions, which is substantially as shown in the XRPD pattern provided in the accompanying drawings of the present invention. At the same time, the measurement of 2θ of the XRPD pattern may have experimental errors, and the measurement of 2θ of the XRPD pattern may be slightly different between different instruments and different samples, so the numerical value of the 2θ cannot be considered absolute. According to the instrument conditions used in the test of the present invention, the diffraction peak has an error tolerance of ±0.2°.

[0123] Differential Scanning Calorimetry (DSC) is a technique that measures the energy difference between a sample and an inert reference material (usually α-Al2O3) as a function of temperature by continuously heating or cooling the sample under program control. The height of the melting peak of the DSC curve depends on many factors related to sample preparation and instrument geometry, while the peak position is relatively insensitive to experimental details. Therefore, in some embodiments, the crystal form described in the present invention is characterized by a DSC graph with a characteristic peak position, which is substantially as shown in the DSC graph provided in the accompanying drawings of the present invention. At the same time, DSC spectra may have experimental errors, and the peak positions and peak values ​​of DSC spectra may vary slightly between different instruments and different samples. Therefore, the peak position or peak value of the DSC endothermic peak cannot be considered absolute. According to the instrument conditions used in the test of the present invention, the melting peak has an error tolerance of ±3°C.

[0124] Glass transition refers to the transition of an amorphous material between a highly elastic state and a glassy state, and is an inherent property of the material; its corresponding transition temperature is the glass transition temperature (Tg), which is an important physical property of amorphous materials. Glass transition is a phenomenon related to molecular motion. Therefore, the glass transition temperature (Tg) mainly depends on the structure of the material and is relatively insensitive to experimental details. In some embodiments, the glass transition temperature (Tg) of the amorphous material described in the present invention is measured by differential scanning calorimetry (DSC), and is characterized by having a glass transition temperature of 107.44°C. According to the conditions of the instruments used in the test of the present invention, the glass transition temperature has an error tolerance of ±3°C.

[0125] Differential scanning calorimetry (DSC) can also be used to detect and analyze whether there is crystal transformation or mixed crystal phenomenon.

[0126] Solids with the same chemical composition often form isomers with different crystal structures, or variants, under different thermodynamic conditions. This phenomenon is called polymorphism or polyphasic phenomenon. When the temperature and pressure conditions change, the variants will transform into each other, and this phenomenon is called crystal transformation. Due to the crystal transformation, the mechanical, electrical, magnetic and other properties of the crystal will undergo great changes. When the temperature of the crystal transformation is within the measurable range, this transformation process can be observed on the differential scanning calorimetry (DSC) graph, which is characterized in that the DSC graph has an exothermic peak reflecting this transformation process, and at the same time has two or more endothermic peaks, which are the characteristic endothermic peaks of different crystal forms before and after the transformation. The crystalline form or amorphous form of the compound of the present invention can undergo crystal transformation under appropriate conditions.

[0127] Thermogravimetric analysis (TGA) is a technique that measures the mass change of a substance with temperature under program control. It is suitable for examining the loss of solvent from crystals or the sublimation and decomposition of samples, and can infer the presence of water of crystallization or solvent in the crystals. The mass change shown by the TGA curve depends on many factors, including sample preparation and instrumentation; the mass change detected by TGA varies slightly between different instruments and samples. Based on the instrumentation used in the present test, the mass change has an error tolerance of ±0.3%.

[0128] In the context of the present invention, the 2θ values ​​in the X-ray powder diffraction pattern are all in degrees (°).

[0129] When referring to a spectrum and / or data appearing in a graph, a "peak" refers to a feature that can be identified by one skilled in the art and is not attributable to background noise.

[0130] The term "substantially as shown" means that at least 50%, or at least 60%, or at least 70%, or at least 80%, or at least 90%, or at least 95%, or at least 99% of the peaks in the X-ray powder diffraction pattern or DSC pattern or TGA results are shown in its pattern.

[0131] "Substantially pure" means that one crystalline form is substantially free of one or more other crystalline forms, that is, the purity of the crystalline form is at least 80%, or at least 85%, or at least 90%, or at least 93%, or at least 95%, or at least 98%, or at least 99%, or at least 99.5%, or at least 99.6%, or at least 99.7%, or at least 99.8%, or at least 99.9%, or the crystalline form contains other crystalline forms, and the percentage of the other crystalline forms in the total volume or total weight of the crystalline form is less than 20%, or less than 10%, or less than 5%, or less than 3%, or less than 1%, or less than 0.5%, or less than 0.1%, or less than 0.01%.

[0132] "Substantially free" means that the percentage of one or more other crystalline forms in the total volume or total weight of the crystalline form is less than 20%, or less than 10%, or less than 5%, or less than 4%, or less than 3%, or less than 2%, or less than 1%, or less than 0.5%, or less than 0.1%, or less than 0.01%.

[0133] “Relative intensity” refers to the ratio of the intensity of other peaks to the intensity of the first strongest peak among all diffraction peaks in an X-ray powder diffraction pattern (XRPD) when the intensity of the first strongest peak is 100%.

[0134] In the context of the present invention, when or whether the word "about" or "approximately" is used, it means within 10%, suitably within 5%, and especially within 1% of a given value or range. Alternatively, for those of ordinary skill in the art, the term "about" or "approximately" means within an acceptable standard error of the mean. Whenever a number having a value of N is disclosed, any number having a value of N + / - 1%, N + / - 2%, N + / - 3%, N + / - 5%, N + / - 7%, N + / - 8% or N + / - 10% is expressly disclosed, where "+ / -" means plus or minus.

[0135] The term "comprising" is an open expression, that is, including the contents specified in the present invention, but not excluding other contents. BRIEF DESCRIPTION OF THE DRAWINGS

[0136] FIG1 is an XRPD diagram of maleate crystalline form A according to an embodiment of the present invention;

[0137] FIG2 is a DSC and TGA diagram of maleate crystalline form A according to an embodiment of the present invention;

[0138] FIG3 is an NMR graph of maleate salt form A according to an embodiment of the present invention: (a) comparison with the free state; (b) integration result;

[0139] FIG4 is a DVS curve of maleate crystalline form A according to an embodiment of the present invention;

[0140] FIG5 is an XRPD pattern of maleate salt form A before and after DVS testing according to an embodiment of the present invention;

[0141] FIG6 is an XRPD pattern of maleate crystalline form B according to an embodiment of the present invention;

[0142] FIG7 is a DSC and TGA diagram of maleate crystalline form B according to an embodiment of the present invention;

[0143] FIG8 is an NMR diagram of maleate crystalline form B according to an embodiment of the present invention;

[0144] FIG9 is an XRPD diagram of a fumarate salt form C according to an embodiment of the present invention;

[0145] Figure 10 is a DSC and TGA diagram of the fumarate crystalline form C according to an embodiment of the present invention;

[0146] FIG11 is an NMR graph of the fumarate salt form C according to an embodiment of the present invention: (a) comparison with the free state; (b) integration result;

[0147] FIG12 is an XRPD pattern of hydrochloride crystal form D according to an embodiment of the present invention;

[0148] FIG13 is a DSC and TGA diagram of hydrochloride crystal form D according to an embodiment of the present invention;

[0149] FIG14 is an NMR graph of hydrochloride crystal form D according to an embodiment of the present invention: (a) comparison with the free state; (b) integration result;

[0150] FIG15 is an XRPD pattern of hydrochloride crystal form E according to an embodiment of the present invention;

[0151] FIG16 is a DSC and TGA diagram of hydrochloride salt form E according to an embodiment of the present invention;

[0152] FIG17 is an NMR graph of hydrochloride crystal form E according to an embodiment of the present invention: (a) comparison with the free state; (b) integration result;

[0153] FIG18 is an XRPD pattern of hydrochloride Form F according to an embodiment of the present invention;

[0154] FIG19 is a DSC and TGA diagram of hydrochloride Form F according to an embodiment of the present invention;

[0155] FIG20 is an NMR graph of hydrochloride salt form F according to an embodiment of the present invention: (a) comparison with the free state; (b) integration result;

[0156] Figure 21 is an XRPD pattern of sulfate crystal form G according to an embodiment of the present invention;

[0157] FIG22 is a DSC and TGA diagram of sulfate crystal form G according to an embodiment of the present invention;

[0158] FIG23 is an NMR graph of sulfate crystal form G according to an embodiment of the present invention: (a) comparison with the free state; (b) integration result;

[0159] FIG24 is an XRPD pattern of succinate salt Form H according to an embodiment of the present invention;

[0160] Figure 25 is a DSC and TGA diagram of the succinate salt form H according to an embodiment of the present invention;

[0161] FIG26 is an NMR graph of the succinate salt form H according to an embodiment of the present invention: (a) comparison with the free state; (b) integration result;

[0162] Figure 27 is an XRPD pattern of succinate salt Form J according to an embodiment of the present invention;

[0163] FIG28 is a DSC and TGA diagram of succinate salt Form J according to an embodiment of the present invention;

[0164] FIG29 is an NMR graph of the succinate salt form J according to an embodiment of the present invention: (a) comparison with the free state; (b) integration result;

[0165] FIG30 is an XRPD pattern of glycolate crystalline Form K according to an embodiment of the present invention;

[0166] FIG31 is a DSC and TGA diagram of glycolate crystalline form K according to an embodiment of the present invention;

[0167] FIG32 is an NMR graph of glycolate crystalline form K according to an embodiment of the present invention: (a) comparison with the free state; (b) integration result;

[0168] FIG33 is an XRPD pattern of benzoic acid cocrystal Form L according to an embodiment of the present invention;

[0169] FIG34 is a DSC and TGA diagram of benzoic acid cocrystal Form L according to an embodiment of the present invention;

[0170] FIG35 is an NMR graph of benzoic acid cocrystal Form L according to an embodiment of the present invention: (a) comparison with the free state; (b) integration result;

[0171] FIG36 is an XRPD pattern of benzoic acid cocrystal Form M according to an embodiment of the present invention;

[0172] FIG37 is a DSC and TGA diagram of benzoic acid cocrystal Form M according to an embodiment of the present invention;

[0173] FIG38 is an NMR graph of benzoic acid cocrystal Form M according to an embodiment of the present invention: (a) comparison with the free state; (b) integration result;

[0174] FIG39 is an XRPD pattern of Form N according to an embodiment of the present invention;

[0175] FIG40 is a DSC and TGA diagram of Form N according to an embodiment of the present invention;

[0176] FIG41 is an NMR diagram of Form N according to an embodiment of the present invention;

[0177] FIG42 is an XRPD pattern of Form O according to an embodiment of the present invention;

[0178] FIG43 is a DSC and TGA diagram of Form O according to an embodiment of the present invention;

[0179] FIG44 is an NMR graph of Form O according to an embodiment of the present invention;

[0180] FIG45 is an XRPD pattern of Form P according to an embodiment of the present invention;

[0181] FIG46 is a DSC and TGA diagram of Form P according to an embodiment of the present invention;

[0182] FIG47 is an NMR diagram of Form P according to an embodiment of the present invention;

[0183] FIG48 is an XRPD pattern of Form Q according to an embodiment of the present invention;

[0184] FIG49 is a DSC and TGA diagram of Form Q according to an embodiment of the present invention;

[0185] FIG50 is an XRPD pattern of Form R according to an embodiment of the present invention;

[0186] FIG51 is a DSC and TGA diagram of Form R according to an embodiment of the present invention;

[0187] FIG52 is an NMR graph of Form R according to an embodiment of the present invention;

[0188] FIG53 is an XRPD pattern of Form S according to an embodiment of the present invention;

[0189] FIG54 is a DSC and TGA diagram of Form S according to an embodiment of the present invention;

[0190] FIG55 is an NMR graph of Form S according to an embodiment of the present invention;

[0191] FIG56 is an XRPD pattern of Form T according to an embodiment of the present invention;

[0192] FIG57 is a DSC and TGA diagram of Form T according to an embodiment of the present invention;

[0193] FIG58 is an NMR graph of Form T according to an embodiment of the present invention;

[0194] FIG59 is an XRPD pattern of Form U according to an embodiment of the present invention;

[0195] FIG60 is a DSC and TGA diagram of Form U according to an embodiment of the present invention;

[0196] FIG61 is an NMR graph of Form U according to an embodiment of the present invention: (a) comparison with the free state; (b) integration result;

[0197] Figure 62 is an XRPD pattern of the stability study of maleate crystalline Form A according to an embodiment of the present invention;

[0198] Figure 63 is an XRPD pattern of the stability study of the fumarate salt Form C according to an embodiment of the present invention;

[0199] FIG64 is an XRPD diagram of a stability study of Form N according to an embodiment of the present invention;

[0200] Figure 65 is an XRPD pattern of stability study of Form S according to an embodiment of the present invention;

[0201] Figure 66 is a comparative XRPD diagram of the solid remaining after maleate crystalline Form A was shaken in a medium for 24 hours according to an embodiment of the present invention;

[0202] Figure 67 is a comparison diagram of XRPD of the solid remaining after the fumarate crystal form C according to an embodiment of the present invention was shaken in a medium for 24 hours. DETAILED DESCRIPTION

[0203] The present application is described in detail below by way of examples, but this does not necessarily mean that there are any adverse limitations on the present application. The present application has been described in detail herein, and specific embodiments thereof have been disclosed. It will be apparent to those skilled in the art that various changes and modifications can be made to the specific embodiments of the present application without departing from the spirit and scope of the present application.

[0204] Unless otherwise specified, the raw materials used in the present invention are commercially available.

[0205] The present application is described in detail below by way of examples, but this does not necessarily mean that there are any adverse limitations on the present application. The present application has been described in detail herein, and specific embodiments thereof have been disclosed. It will be apparent to those skilled in the art that various changes and modifications can be made to the specific embodiments of the present application without departing from the spirit and scope of the present application.

[0206] General analytical methods:

[0207] 1. NMR analysis ( 1 H NMR)

[0208] Several milligrams of solid sample were dissolved in dimethyl sulfoxide-d6 solvent and subjected to nuclear magnetic resonance analysis on a Bruker AVANCE-III (Bruker, Germany).

[0209] 2. X-ray powder diffraction (XRPD)

[0210] Instrument model: Bruker D8ADVANCE (instrument uniqueness number: IARC-031-PXRD-01).

[0211] Testing basis: General Chapter 0451, Part 4, 2020 edition of the Chinese Pharmacopoeia.

[0212] Sample preparation: Place the sample in the center of the sample holder groove and make the sample surface level with the sample holder surface.

[0213] Experimental conditions: CuKa 40kV 40mA, divergence slit 0.6mm, Soller slit 4.0°, continuous scanning, detector: LynxEye.

[0214] Step size: 0.02°.

[0215] Scanning speed: 4° / min.

[0216] 3. Thermogravimetric analysis (TGA)

[0217] The thermogravimetric analyzer (TA Discovery 55, TA, US) was used. A 2-5 mg sample was placed in a equilibrated open aluminum sample pan and automatically weighed in the TGA furnace. The sample was heated to the final temperature at a rate of 10°C / min. A nitrogen purge rate of 60 mL / min was maintained at the sample and 40 mL / min at the balance.

[0218] 4. Differential Scanning Calorimetry (DSC)

[0219] The differential scanning calorimeter was a TA Discovery 2500 (TA, US). 1-2 mg of sample was accurately weighed and placed in a perforated DSC Tzero sample pan. The sample was heated to the final temperature at a rate of 10°C / min, with nitrogen purge rate of 50 mL / min.

[0220] 5. Dynamic moisture adsorption and desorption analysis (DVS)

[0221] Dynamic moisture sorption / desorption analysis was performed using a DVS Intrinsic (SMS, UK). The test used a gradient profile with humidity changes from 50% to 95% to 0% to 50%, with each gradient increasing by 10% within the 0% to 90% range. The gradient endpoint was determined using the dm / dt method, with a dm / dt of less than 0.002% maintained for 10 minutes. After completion of the test, the samples were analyzed by XRPD to confirm any changes in the solid form.

[0222] 6. Polarized light microscopy (PLM)

[0223] A polarizing microscope was used, Nikon Ci-POL (Nikon, JP). A small amount of sample was placed on a glass slide and an appropriate lens was selected to observe the sample morphology.

[0224] 7. High Performance Liquid Chromatography (HPLC)

[0225] The high performance liquid chromatography model was LC-2030C 3D Plus (Shimadzu, JP), and the test conditions were shown in Table 21.

[0226] Table 21

[0227] The HPLC conditions used in the maleate content test are shown in Table 22 below.

[0228] Table 22

[0229] 8. Ion Chromatography (IC)

[0230] The ion chromatograph model was ICS 5000 (Thermo Fisher, US), and the instrument parameters are shown in Table 23.

[0231] Table 23

[0232] General test methods:

[0233] 1. Raw material solubility test

[0234] Weigh approximately 20 mg of sample into an EP tube. Add a defined amount of solvent incrementally at room temperature (~25°C). Stir the solution and observe whether the solid is completely dissolved. If the solid remains insoluble after adding 10.0 mL of solvent, discontinue the experiment. Estimate the solubility of the compound in the solvent based on the volume of solvent used to completely dissolve the solid.

[0235] 2. Reaction crystallization method

[0236] 2.1 1 equivalent feed

[0237] Add approximately 26 mg (0.05 mmol) of sample and 1 equivalent of the acidic compound to a predetermined amount of the selected solvent. Suspend at room temperature for 2 days. Centrifuge the suspension, and dry the solid under vacuum at room temperature. If the solution is clear, place it in a refrigerator (-15°C). If a solid phase precipitates, remove the supernatant by centrifugation and dry it under vacuum at room temperature. If no solid phase precipitates after cooling, add the antisolvent dropwise until solid precipitates.

[0238] 2.2 2 equivalent feeding

[0239] About 26 mg (0.05 mmol) of sample and 2 equivalents of acidic compound were added to a certain amount of selected solvent, suspended at room temperature for 2 days, the suspension was centrifuged, and the solid was dried under vacuum at room temperature.

[0240] 3. Solvent evaporation method

[0241] The clear solution obtained from the solubility test of the raw material is left to stand at room temperature in an open air until the solvent is completely evaporated to obtain a solid, or about 20 mg of the raw material is weighed, and an appropriate amount of the selected solvent is added dropwise to a certain amount of poor solvent until it is completely dissolved, and the solution is left to stand at room temperature to evaporate until the solvent is completely evaporated.

[0242] 4. Suspension method

[0243] 4.1. Room temperature suspension

[0244] Using different crystal forms as starting materials, a certain amount of sample is added to a selected single solvent or binary solvent until a suspension is formed. After suspension and stirring at room temperature for a certain period of time, the suspension is centrifuged and the solid is vacuum dried at room temperature.

[0245] 4.2, 50℃ suspension

[0246] Using different crystal forms as starting materials, a certain amount of sample was added to the selected solvent until a suspension was formed. After suspension and stirring at 50° C. for 1 day, the suspension was centrifuged and the solid was vacuum dried at room temperature.

[0247] 5. Dissolution crystallization method

[0248] 5.1 Dissolution crystallization method

[0249] Weigh approximately 20 mg of sample and add a sufficient amount of good solvent at room temperature to completely dissolve the sample, or prepare a saturated solution of the good solvent. Add the solution dropwise to a 5-10 times volume of the poor solvent. Stir for 1 hour, centrifuge any solid precipitates, and vacuum dry the solid at room temperature. Continue stirring for 24 hours for a clear solution. If no solid precipitates remain, place the solution in a refrigerator at 4 or -15°C, centrifuge any solid precipitates, and vacuum dry the solid at room temperature.

[0250] 5.2 Binary Solvent Forward Drop Method

[0251] Weigh approximately 20 mg of sample and add a sufficient amount of good solvent at room temperature to completely dissolve the sample or prepare a saturated solution of the good solvent. Then, add a poor solvent dropwise until solid precipitates. Stir at room temperature for 15 minutes, centrifuge any solid precipitates, and vacuum dry the solid at room temperature. Continue stirring the clarified solution for 24 hours. If no solid precipitates remain, place the solution in a refrigerator at 4 or -15°C, centrifuge any solid precipitates, and vacuum dry the solid at room temperature.

[0252] 6. Cooling method

[0253] 6.1. Single Solvent Cooling

[0254] Weigh approximately 20 mg of sample and add preheated solvent of your choice dropwise at 50°C until the solid is completely dissolved. Quickly transfer the solution to room temperature and cool. Allow to stand at room temperature for at least 2 hours. If sufficient solid does not precipitate, cool the solution further at 4°C. If sufficient solid still does not precipitate, cool the solution further at -15°C. For systems with sufficient solid precipitation, centrifuge and dry the solid under vacuum at room temperature.

[0255] 6.2. Binary Solvent Cooling

[0256] Weigh approximately 20 mg of sample and mix with a suitable amount of poor solvent at 50°C to form a suspension. Gradually add preheated good solvent dropwise until the solid is completely dissolved. Transfer the solution to room temperature and cool. Let it stand at room temperature for at least 2 hours. If sufficient solid does not precipitate, cool the solution to 4°C further. If sufficient solid still does not precipitate, cool the solution to -15°C further. For systems with sufficient solid precipitation, centrifuge and dry the solid under vacuum at room temperature.

[0257] 7. Gas Diffusion Method

[0258] Weigh approximately 20 mg of sample and dissolve it in a good solvent or a saturated solution of a good solvent. Place the clear solution in a poor solvent atmosphere and let it stand at room temperature until solid precipitates. Remove the solution from the system with solid precipitation using a syringe and perform XRPD analysis on the wet sample.

[0259] 8. Solid gas diffusion

[0260] Weigh about 20 mg of amorphous sample and place it in a selected solvent atmosphere at room temperature or low temperature for 7 days. Regularly observe the properties of the solid in the glass vial and perform XRPD analysis on the solid.

[0261] 9. Thermal transfer

[0262] Thermal crystallization was performed using an Instec HCS424GXY hot stage (Instec Inc., USA). A 6-8 mg sample was placed on a glass slide on the hot stage and heated to the target temperature at a rate of 20°C / min. The temperature was kept constant for 5-10 min, and then naturally cooled to room temperature to obtain a solid.

[0263] 10. Competitive water activity suspension experiment

[0264] Weigh equal amounts of the selected crystalline form sample and add them to a certain volume of a saturated water / isopropanol solution with varying water contents (0%, 30%, and 60%, water by volume). Suspend and stir at room temperature and 60°C for a specified period of time. The suspension is centrifuged, and the wet sample is characterized by XRPD.

[0265] 11. Stability study

[0266] About 20 mg of sample was weighed and placed in a weighing bottle, which was then placed under high temperature (60°C), high humidity (25°C / 92.5% RH), light (25°C / 4500 Lux), and acceleration (40°C / 75% RH). Samples were taken for XRPD characterization after 7 and 15 days.

[0267] 12. Solubility test

[0268] The preparation process of the bio-media is shown in Table 24. Samples of different crystalline forms were added to the bio-media and shaken at 37°C for 24 hours. Samples were taken at 0.5, 2, and 24 hours. The sampled solutions were filtered through a 0.22 μm water filter. Some samples with higher concentrations were appropriately diluted with diluent. The signal peak area of ​​the solution was measured by HPLC. Finally, the concentration of the compound in the solution was calculated based on the peak area, the HPLC standard curve of the raw material, and the dilution factor. In addition, the pH value of the supernatant after 24 hours was measured, and the remaining solid was analyzed by XRPD.

[0269] Table 24

[0270] Example 1 Preparation of the compound represented by formula (I)

[0271] At room temperature, p-toluenesulfonyl chloride (21.9 g, 115 mmol) was added to a solution of 7-chloro-1,2,3,4-tetrahydrobenzo[B]azepin-5-one (15 g, 76.7 mmol) in pyridine (150 mL). The reaction mixture was allowed to react at room temperature for 16 hours. The mixture was concentrated under reduced pressure, poured into water (200 mL), and extracted with ethyl acetate (100 mL x 3). The organic phases were combined. The organic phases were washed with saturated sodium chloride solution (100 mL), dried over anhydrous sodium sulfate, and filtered. The filtrate was concentrated under reduced pressure to remove the organic solvent, and the residue was purified by silica gel chromatography to obtain intermediate I-1.

[0272] LC-MS (ESI) [M+H] + 349.9.

[0273] 1 H NMR (400MHz, CDCl3) δ7.66(d,J=2.4Hz,1H),7.58(d,J=8.3Hz,2H),7.47(dd,J=8.6,2.5Hz,1H),7.43(d,J=8 .5Hz,1H),7.28(d,J=8.0Hz,2H),3.83(t,J=6.5Hz,2H),2.43(s,3H),2.40–2.35(m,2H),2.00–1.91(m,2H).

[0274] At 25°C, intermediate I-1 (37.00 g, 106.00 mmol) was dissolved in anhydrous tetrahydrofuran (350 mL). Under argon protection and ice-water bath cooling, sodium hydride (6.36 g, 60% wt, 159.00 mmol) was added portionwise. After stirring in an ice-water bath for 1 hour, dimethyl carbonate (19.08 g, 212.00 mmol) was added and the temperature was raised to 50°C and stirred for 24 hours. After cooling, the reaction solution was slowly poured into cold saturated aqueous ammonium chloride (500 mL), concentrated to remove most of the tetrahydrofuran, and filtered. The filter cake was washed with water, then slurried with petroleum ether, filtered, and drained to obtain intermediate I-2.

[0275] LC-MS (ESI) [M+H] + 408.0.

[0276] At 25°C, intermediate I-2 (19.00 g, 46.68 mmol) was dissolved in anhydrous N,N-dimethylformamide (187 mL). Sodium carbonate (14.84 g, 140.00 mmol) and 2-(2-bromoethyl)isoindoline-1,3-dione (23.71 g, 93.36 mmol) were added sequentially. The mixture was stirred at 90°C overnight under argon. The reaction mixture was cooled and diluted with ethyl acetate (500 mL). The mixture was washed with water (150 mL x 3) and saturated brine (100 mL), dried over anhydrous sodium sulfate, filtered, and the filtrate was concentrated under reduced pressure to obtain the crude product. The crude product was separated and purified by silica gel chromatography to obtain intermediate I-3.

[0277] LC-MS (ESI) [M+H] + 581.2.

[0278] At 25°C, intermediate I-3 (20.00 g, 34.48 mmol) was dissolved in dimethyl sulfoxide / water (130 mL / 13 mL), and sodium chloride (16.70 g, 28.60 mmol) was added. The system was purged with argon three times, and stirred at 150°C under argon for 10 hours. The reaction mixture was cooled, diluted with ethyl acetate (400 mL), washed with water (150 mL × 3), washed with saturated brine (100 mL), dried over anhydrous sodium sulfate, filtered, and the filtrate concentrated under reduced pressure to obtain the crude product. The crude product was separated and purified by silica gel chromatography to obtain intermediate I-4.

[0279] LC-MS (ESI) [M+H] + 523.2.

[0280] At 25°C, intermediate I-4 (200 mg, 0.38 mmol) was dissolved in ethanol (7 mL). 85% hydrazine hydrate (0.35 mL) was added, and the reaction mixture was stirred at 35°C for 4 hours. The reaction mixture was concentrated under reduced pressure to remove most of the ethanol, diluted with ethyl acetate (50 mL), and washed sequentially with water (20 mL × 3) and saturated brine (20 mL). The mixture was dried over anhydrous sodium sulfate, filtered, and the filtrate was concentrated under reduced pressure to obtain the crude intermediate I-5. The crude product was used directly in the next reaction.

[0281] LC-MS (ESI) [M+H] + 375.2.

[0282] Intermediate I-5 (170 mg, 0.45 mmol) was dissolved in methanol (10 mL) at 25°C. Sodium borohydride (190 mg, 5.00 mmol) was slowly added under ice-water cooling. The reaction mixture was stirred at room temperature for 1 hour, then concentrated under reduced pressure to remove most of the methanol. The mixture was diluted with ethyl acetate (50 mL), washed sequentially with water (20 mL × 3) and saturated brine (20 mL), dried over anhydrous sodium sulfate, and filtered. The filtrate was concentrated under reduced pressure to obtain the crude intermediate I-6. The crude product was used directly in the next reaction.

[0283] LC-MS (ESI) [M+H] + 377.2.

[0284] At 25°C, intermediate I-6 (150 mg, 0.40 mmol) was dissolved in anhydrous methanol (20 mL) and magnesium turnings (2.00 g, 83.33 mmol) were added. The nitrogen atmosphere was replaced three times and the mixture was stirred at 70°C overnight under a nitrogen atmosphere (balloon). After cooling, the mixture was filtered through a pad of celite. The filtrate was concentrated to dryness and dissolved in a mixture of dichloromethane and methanol (10 / 1, 50 mL). The mixture was washed with saturated aqueous ammonium chloride (20 mL x 3) and water (20 mL x 2), dried over anhydrous sodium sulfate, and filtered. The filtrate was concentrated under reduced pressure to obtain the crude intermediate I-7. The crude product was used directly in the next reaction.

[0285] LC-MS (ESI) [M+H] + 223.0.

[0286] Intermediate I-7 (7.30 g, 32.89 mmol) and triethylamine (10.10 g, 100.00 mmol) were dissolved in anhydrous dichloromethane (100 mL) at 25°C. Under argon protection and cooling in an ice-water bath, 9-fluorenylmethyl chloroformate (12.73 g, 49.33 mmol) was slowly added and stirred at 25°C for 16 hours. The mixture was concentrated under reduced pressure at room temperature, slurried with petroleum ether, filtered, and the filter cake was washed with water (20 mL) and dried to obtain Intermediate I-47.

[0287] LC-MS (ESI) [M+H] + 444.8.

[0288] At room temperature, methyl 6-aminonicotinate (1.0 g, 6.57 mmol) was dissolved in pyridine (20 mL), and 2-trifluoromethylbenzoyl chloride (1.51 g, 7.25 mmol) was added. After the addition was complete, the reaction mixture was stirred at room temperature for 1 h. The reaction mixture was poured into ice water (100 mL) and extracted with ethyl acetate (50 mL × 3). The combined organic phases were washed with water (50 mL × 5), dried over anhydrous sodium sulfate, filtered, and the filtrate was concentrated under reduced pressure. The residue was separated and purified by silica gel chromatography to obtain intermediate I-12.

[0289] LC-MS (ESI) [M+H] + 325.0.

[0290] At room temperature, intermediate I-12 (1.35 g, 4.16 mmol) was dissolved in tetrahydrofuran (10 mL). A solution of sodium hydroxide (499 mg, 12.5 mmol) in water (2 mL) was added. After the addition was complete, the reaction mixture was stirred at 70°C for 1 hour. After completion of the reaction, the pH of the reaction solution was adjusted to 5-6 with 1N hydrochloric acid. The solid was filtered and dried to obtain intermediate I-13.

[0291] LC-MS (ESI) [M+H] + 311.0.

[0292] At 25°C, intermediate I-47 (4.70 g, 10.58 mmol) was dissolved in anhydrous tetrahydrofuran (35 mL). Pyridine (8.37 g, 106.00 mmol), intermediate I-13 (4.92 g, 15.87 mmol), and 1-propylphosphonic anhydride (50% wt solution in ethyl acetate, 20.00 g, 31.74 mmol) were added sequentially. The mixture was stirred at 65°C overnight under argon. The reaction mixture was cooled, concentrated to remove most of the tetrahydrofuran, and diluted with ethyl acetate (150 mL). The mixture was washed sequentially with 1N hydrochloric acid (100 mL × 2), saturated aqueous sodium bicarbonate (100 mL × 3), water (100 mL), and saturated aqueous sodium chloride (100 mL). The mixture was dried over anhydrous sodium sulfate and filtered. The filtrate was concentrated under reduced pressure to remove the organic solvent to obtain the crude product. The crude product was separated and purified by silica gel chromatography to give intermediate I-48A (Rt = 1.541 min).

[0293] LCMS analysis method: Chromatographic column: Waters acquity UPLC CSH 2.1×50 mm, 1.7 μm.

[0294] Mobile phase: A: water (0.01% trifluoroacetic acid) B: acetonitrile (0.01% trifluoroacetic acid).

[0295] Elution gradient: 5%-95% B in 0.7 min; 95% B in 0.8 min; then 5% B in 0.5 min.

[0296] Flow rate: 1.0 mL / min.

[0297] Column temperature: 60°C.

[0298] Mass spectrometry scan range: 100–1000.

[0299] Intermediate I-48A (Rt = 1.541 min) LC-MS (ESI) [M+H] + 737.3.

[0300] Intermediate I-48A (14 mg, 0.019 mmol) was dissolved in N,N-dimethylformamide (3 mL) at 25°C, and pyrrolidine (35.50 mg, 0.50 mmol) was added. The mixture was stirred at 25°C for 1 hour. The mixture was diluted with ethyl acetate (20 mL), washed with water (10 mL x 3), dried over anhydrous sodium sulfate, and filtered. The filtrate was concentrated under reduced pressure and purified by C18 reverse-phase chromatography (formic acid system) to yield compound 8.

[0301] LC-MS (ESI) [M+H] + 515.2.

[0302] 1 H NMR(400MHz,DMSO-d6)δ11.18(s,1H),8.13–7.90(m,2H),7.88–7.52(m,6H),7.09( dd,J=8.3,2.7Hz,1H),6.89(d,J=8.3Hz,1H),4.90(dt,J=13.7,3.3Hz,1H),4.14(d ,J=9.2Hz,1H),3.80–3.35(m,1H),3.15–3.03(m,1H),3.03–2.92(m,1H),2.66(t,J =12.7Hz,1H),2.09(dd,J=12.1,4.1Hz,2H),1.86–1.64(m,2H),1.64–1.51(m,1H).

[0303] Compound 8 was chiral resolved by SFC to give compound 10A (Rt=1.424 min).

[0304] Chiral separation method:

[0305] Instrument: MGⅡpreparative SFC (SFC-14).

[0306] Chromatographic column: ChiralPak AD, 250×30 mm ID, 10 μm.

[0307] Mobile phase: A: carbon dioxide B: ethanol (0.1% ammonia water).

[0308] Elution gradient: 35% B.

[0309] Flow rate: 80 mL / min.

[0310] Back pressure: 100bar.

[0311] Column temperature: 38°C.

[0312] Detection wavelength: 220nm.

[0313] Cycle time: ~8min.

[0314] Chiral analysis method:

[0315] Instrument: Waters UPC2 analytical SFC (SFC-H).

[0316] Chromatographic column: ChiralPak AD, 150×4.6mm ID, 3μm.

[0317] Mobile phase: A: carbon dioxide B: ethanol (0.05% diethylamine).

[0318] Elution gradient: 40% B.

[0319] Flow rate: 2.5 mL / min.

[0320] Back pressure: 1500psi.

[0321] Column temperature: 35℃.

[0322] Detection wavelength: 220nm.

[0323] Compound 10A:

[0324] Rt=1.424min.

[0325] LC-MS (ESI) [M+H] + 515.2.

[0326] 1H NMR (400MHz, DMSO-d6) δ11.18(s,1H),8.30–7.88(m,2H),7.88–7.55(m,6H),7.10(dd,J=8.4,2.7Hz,1H),6.89(d,J=8.3Hz,1H),4.90(dt,J= 13.5, 3.2Hz, 1H), 4.14 (d, J = 9.2Hz, 1H), 3.40–3.39 (m, 1H), 3.13–2.90 (m, 2H), 2.66 (t, J = 12.3Hz, 1H), 2.16–2.05 (m, 2H), 1.87–1.49 (m, 3H).

[0327] Example 2 Inhibitory Effect of Compounds of Formula (I) on Vasopressin-Induced Activation of Vasopressin Receptor V2R 50 test

[0328] (1) Cells

[0329] HeLa cell line stably expressing human vasopressin receptor V2R (HeLa-V2R): constructed by Shanghai GeneChem Technology Co., Ltd. using lentiviral infection method, and verified by qPCR to stably express human V2R.

[0330] (2) Reagents

[0331] DMEM cell culture medium: Brand: Gibco, Catalog Number: 11995065; Fetal bovine serum: Brand: Jitai, Catalog Number: FND500; 0.25% trypsin: Brand: Gibco, Catalog Number: 25200072; Puromycin Dihydrochloride: Brand: Gibco, Catalog Number: A1113803; cAMP-GS HIRANGE KIT: Brand: Cisbio, Catalog Number: 62AM6PEC; IBMX: Brand: Sigma, Catalog Number: i5879; Vasopressin AVP: Customized by Jier Biochemical (Shanghai) Co., Ltd.

[0332] (3) Test method

[0333] HeLa-V2R cells were cultured in DMEM supplemented with 10% fetal bovine serum at 37°C and 5% CO2. 2 μg / mL puromycin was added to the culture medium to continuously select cells expressing V2R. On the day of the experiment, the cells were trypsinized, washed twice with the stimulation buffer in the cAMP-GS HIRANGE kit, resuspended, counted, and prepared into 1.6×10 6cells / ml, add IBMX to a final concentration of 0.5mM. Transfer 5μL of cell suspension / well to a 384-well plate, and add 2.5μL of different concentrations of the test compound (3-fold dilution starting from 10μM, 10 concentration gradients) or DMSO (Minimum value, Maximum value control) to the corresponding wells. After incubation at room temperature for 30 minutes, add 2.5μL of vasopressin AVP solution to the test compound well and the maximum value well to a final concentration of 2.25nM, add 2.5μL of stimulation buffer to the minimum value well, and incubate at 25 degrees for 60 minutes. At the same time, prepare cAMP standard samples (3-fold dilution starting from 5.6μM, 10 concentration points), and transfer 10μL of cAMP standard to the corresponding wells of the 384-well plate. Dilute the cAMP-d2 fluorescent and anti-cAMP antibody probes provided in the cAMP-GS HIRANGE kit 20-fold with the lysis buffer in the kit. Add 5 μL of each to each well of a 384-well plate, mix thoroughly, and briefly centrifuge. Incubate at 25°C for 2 hours before assaying. Samples were assayed using the HTRF method on an Envision microplate reader, measuring fluorescence intensity at 615 nm and 665 nm. Duplicate wells were prepared for each sample, and 32 replicate wells were prepared for both the Min and Max wells.

[0334] (4) Data processing

[0335] Calculate the fluorescence intensity ratio FI of each well sample at 665nm and 615nm wavelength 665 / 615 The logarithm of the standard concentration is X, FI 665 / 615 X1000 is the Y value, and the standard curve is obtained by fitting the "log (inhibitor) vs response–variable slope (four parameters)" model in Prism 8.0 software. 665 / 615 X1000 is the Y value, and the cAMP concentration corresponding to each sample was calculated based on the above standard curve in Prism 8.0 software.

[0336] The formula for calculating %Inhibition is as follows:

[0337] in is the average calculated value of cAMP concentration in all maximum value wells; is the average calculated value of cAMP concentration in all minimum value wells; Ccmpd is the calculated value of cAMP concentration of the test compound.

[0338] IC was calculated by nonlinear regression using the "log (inhibitor) vs response–variable slope (four parameters)" model in Prism 8.0 software, with % Inhibition as the Y value and the logarithm of compound concentration as the X value. 50 , where Y = Bottom + (Top - Bottom) / (1 + 10^((LogIC 50 -X)*Hill Slope)).

[0339] The experimental results are shown in Table 25:

[0340] Table 25: Evaluation of the compounds on the inhibition of cAMP increase in human cervical cancer cells (Human V2R Hela-Stable cell line OE2)

[0341] Example 3 Salt type screening

[0342] Fifteen acidic compounds were selected for salt screening using the reactive crystallization method. The results are shown in Tables 26 and 27 below.

[0343] Table 26 Solution suspension method (1 equivalent) salt type initial screening experiment

[0344] Note: "*" indicates that the solution was clarified after suspension and solids were precipitated when placed at -15°C; "**" indicates that the solution was clarified after suspension and cooling to -15°C and solids were precipitated when n-heptane was added.

[0345] Table 27 Solution suspension method (2 equivalents) salt type initial screening experiment

[0346] As can be seen from the above table, the compound represented by formula (I) can form 6 salts, namely hydrochloride, sulfate, maleate, fumarate, succinate and glycolate.

[0347] Example 4 Preparation of Maleate Crystalline Form A

[0348] Method 1: Weigh 513.6 mg of the compound of formula (I) and 1 equivalent of maleic acid, add 16 mL of isopropanol, and stir at room temperature for 2 days. Centrifuge the suspension, and vacuum dry the solid at 40°C for 3 days. 611.5 mg of maleate salt Form A was obtained.

[0349] Method 2: Methanol (30 mL, 10.0 v / w) was added to the jacketed reactor R1 at room temperature; nitrogen was replaced three times; free amine (3.0 g, 1 w, 5.82 mmol, 1.0 eq.) was added to the jacketed reactor R1 at room temperature and stirring was started; stirring was performed until dissolved; in the jacketed reactor R2, an isopropanol solution of maleic acid was prepared: maleic acid (0.71 g, 0.236 w, 6.11 mmol, 1.05 eq) was dissolved in isopropanol (60 mL, 20.0 v / w) at 25-30°C; the prepared maleic acid / isopropanol solution was added dropwise to the reactor R1, the internal temperature was controlled at 20-30°C, and the addition time was 20 minutes; after the addition was completed, the reaction was carried out at 20-30°C for 2-5 hours; the filter cake was washed once with isopropanol (9 mL, 3.0 v / w), and dried to obtain maleate salt Form A.

[0350] Method 3: Add 10 L of methanol to a 100 L reactor, add 4.2 kg of free base, add 6.8 L of methanol, raise the temperature to 60 ° C, dissolve 993 g of maleic acid in 33.6 L of isopropanol, slowly add the above solution dropwise, cool to 25 ° C, and filter to obtain 4.7 kg of maleate salt form A.

[0351] The maleate salt Form A was characterized, and the results are shown in Figures 1 to 5. XRPD (Figure 1) results show that the maleate salt Form A is a well-crystalline solid. TGA (Figure 2) results show that the maleate salt Form A loses 0.5% weight upon heating to 150°C, and decomposition may occur above 200°C. DSC (Figure 2) results show that the maleate salt Form A has an endothermic peak at 229°C. NMR (Figure 3) results show that compared to the free form, the peaks at 1.50-1.90 ppm, 2.98 ppm, 3.07 ppm, 4.11 ppm, 6.90 ppm, and 7.08 ppm are shifted, suggesting salt formation. A maleic acid signal peak is observed at 6.03 ppm, indicating a 1:1 ratio of raw material to maleic acid based on the integration results. An isopropanol solvent peak is observed at 1.04 ppm, suggesting a small amount of residual isopropanol solvent in the sample. DVS results (Figure 4) show that maleate Form A gained 0.09% weight at 80% RH, gained 0.23% weight at 95% RH, and lost 0.24% weight at 0% RH, indicating that Form A is virtually non-hygroscopic. XRPD results (Figure 5) show that the sample after DVS testing did not undergo any crystal change. This indicates that Form A is a well-crystalline, anhydrous form with virtually no hygroscopicity.

[0352] Example 5 Preparation of Maleate Crystal Form B

[0353] 21.7 mg of maleate salt Form A was dissolved in 0.5 mL of DMF, 1.5 mL of isopropanol was added, and the mixture was heated to 60°C, slowly cooled to 15°C, and filtered to obtain maleate salt Form B.

[0354] XRPD (Figure 6) results show that Form B is a well-crystalline solid. TGA (Figure 7) results show that Form B loses 9.7% weight when heated from room temperature to 170°C, and decomposition may occur above 220°C. DSC (Figure 7) results show that Form B has an endothermic signal corresponding to desolvation at around 145°C and an endothermic peak at around 234°C. NMR (Figure 8) results are basically consistent with the raw material, with DMF solvent peaks visible at 2.73, 2.89, and 7.95 ppm. Based on the integration results, the ratio of compound to DMF is 1:0.9, and the DMF content is basically consistent with the TGA weight loss. The results of the thermal transformation experiment show that Form B transforms to Form A after heating to 170°C for desolvation. In summary, Form B is a DMF solvate.

[0355] Example 6 Preparation of Fumarate Crystalline Form C

[0356] 25.6 mg of the compound represented by formula (I) was added with 0.8 mL of isopropanol and 1 equivalent of fumaric acid. The mixture was stirred at room temperature for 2 days and centrifuged to obtain the fumarate salt form C.

[0357] XRPD (Figure 9) results indicate that the fumarate salt Form C is a well-crystalline solid. TGA (Figure 10) results show a 0.7% weight loss upon heating to 150°C, with possible decomposition occurring after 190°C. DSC (Figure 10) results indicate an endothermic signal at approximately 217°C. NMR (Figure 11) results show shifts in peaks at 1.50-1.90 ppm, 2.98 ppm, 3.07 ppm, 4.11 ppm, 6.90 ppm, and 7.08 ppm compared to the free form, suggesting salt formation. A fumaric acid peak is observed at 6.57 ppm, indicating a 1:1 API to fumaric acid ratio based on integration. An isopropanol solvent peak is observed at 1.04 ppm, suggesting the presence of a small amount of residual isopropanol solvent. In summary, the fumarate salt Form C is an anhydrous form.

[0358] Example 7 Preparation of Hydrochloride Form D

[0359] 25.3 mg of the compound represented by formula (I) was added with 0.8 mL of isopropanol and 1 equivalent of concentrated hydrochloric acid. The mixture was stirred at room temperature for 2 days and centrifuged to obtain hydrochloride crystal form D.

[0360] XRPD (Figure 12) results indicate that Form D hydrochloride is a well-crystalline solid. TGA (Figure 13) results show a 1.6% weight loss (corresponding to the weight loss of 0.5 water molecules) upon heating to 150°C; decomposition may occur after 230°C. DSC (Figure 13) results reveal endothermic signals at approximately 71°C and 262°C. NMR (Figure 14) results show shifts in peaks at 1.50-1.90 ppm, 2.98 ppm, 3.07 ppm, 4.11 ppm, 6.90 ppm, and 7.08 ppm compared to the free form, suggesting salt formation. A solvent peak associated with isopropanol is observed at 1.04 ppm, indicating the presence of a small amount of residual isopropanol solvent. Thermal crystallization experiments indicate that Form D hydrochloride transforms to Form F hydrochloride upon heating to 150°C. Ion chromatography results indicate a 1:1 salt formation ratio for Form D hydrochloride. In summary, Form D hydrochloride is a hydrate.

[0361] Example 8 Preparation of Hydrochloride Form E

[0362] 25.3 mg of the compound represented by formula (I) was added to 1.0 mL of cyclohexane and 1 equivalent of concentrated hydrochloric acid. The mixture was stirred at room temperature for 2 days and centrifuged to obtain hydrochloride crystal form E.

[0363] XRPD (Figure 15) results show that hydrochloride crystal form E is a poorly crystalline solid. TGA (Figure 16) results show that the sample continues to lose weight during heating. DSC (Figure 16) results show endothermic signals at around 89°C and 201°C. NMR (Figure 17) results show that compared with the free state, the 1.50-1.90ppm, 2.98ppm, 3.07ppm, 6.90ppm and 7.08ppm peaks are shifted, suggesting that the sample has formed a salt; a cyclohexane solvent peak is visible at 1.39ppm, suggesting that a small amount of cyclohexane solvent remains in the sample. In summary, hydrochloride crystal form E may be an anhydrate or hydrate that adsorbs water.

[0364] Example 9 Preparation of Hydrochloride Form F

[0365] 25.4 mg of Form N was added to 0.8 ml of isopropanol and 1 N hydrochloric acid, and the mixture was stirred at room temperature for 2 days. The suspension was centrifuged and the solid was dried under vacuum at room temperature to obtain Form F hydrochloride.

[0366] XRPD (Figure 18) results indicate that Form F hydrochloride is a well-crystalline solid. TGA (Figure 19) results indicate a 0.5% weight loss upon heating to 150°C, with possible decomposition occurring after 230°C. DSC (Figure 19) results indicate endothermic signals at approximately 316°C and 320°C. NMR (Figure 20) results indicate shifts in peaks at 1.50-1.90 ppm, 2.98 ppm, 3.07 ppm, 4.11 ppm, 6.90 ppm, and 7.08 ppm compared to the free form, suggesting salt formation. A solvent peak for isopropanol is visible at 1.04 ppm, suggesting the presence of a small amount of residual isopropanol solvent. Ion chromatography results indicate a 1:1 salt formation ratio for Form F hydrochloride. In summary, Form F hydrochloride is an anhydrous form.

[0367] Example 10 Preparation of Sulfate Crystal Form G

[0368] 26.1 mg of the compound represented by formula (I) was added to 1.0 mL of cyclohexane and 1 equivalent of concentrated sulfuric acid. The mixture was stirred at room temperature for 2 days and centrifuged to obtain sulfate salt Form G.

[0369] XRPD (Figure 21) results show that sulfate crystal form G is a well-crystalline solid. TGA (Figure 22) results show that the sample loses 3.7% weight during heating to 150°C and may decompose after 240°C. DSC (Figure 22) results show endothermic signals at around 282°C and 298°C. NMR (Figure 23) results show that compared with the free state, the peaks at 1.50-1.90ppm, 2.98ppm, 3.07ppm, 6.90ppm, and 7.08ppm are shifted, suggesting that the sample has formed a salt; a cyclohexane solvent peak is visible at 1.39ppm, suggesting that the sample contains a very small amount of cyclohexane solvent. In summary, sulfate crystal form G may be an anhydrate or hydrate that adsorbs water.

[0370] Example 11 Preparation of Succinate Form H

[0371] 24.1 mg of the compound represented by formula (I) was added to 0.8 ml of isopropanol and 1 equivalent of succinic acid. The mixture was stirred at room temperature for 2 days and centrifuged to obtain succinate salt form H.

[0372] XRPD (Figure 24) results indicate that Form H succinate salt is a well-crystalline solid. TGA (Figure 25) results indicate a 0.2% weight loss upon heating to 120°C, with possible decomposition occurring after 170°C. DSC (Figure 25) results indicate an endothermic signal at approximately 186°C. NMR (Figure 26) results indicate shifts in peaks at 1.50-1.90 ppm, 2.98 ppm, 3.07 ppm, 4.11 ppm, 6.90 ppm, and 7.08 ppm compared to the free form, suggesting salt formation. A succinic acid peak is observed at 2.39 ppm, indicating a 1:1 API to succinic acid ratio based on integration. An isopropanol solvent peak is observed at 1.04 ppm, suggesting the presence of a small amount of residual isopropanol solvent. In summary, Form H succinate salt is an anhydrous form.

[0373] Example 12 Preparation of Succinate Form J

[0374] 24.7 mg of the compound represented by formula (I) was added with 1.0 mL of methyl tert-butyl ether and 1 equivalent of succinic acid. The mixture was stirred at room temperature for 2 days and centrifuged to obtain succinate salt Form J.

[0375] XRPD (Figure 27) results indicate that Form J succinate salt is a well-crystalline solid. TGA (Figure 28) results indicate a 0.6% weight loss upon heating to 150°C, with possible decomposition occurring after 170°C. DSC results indicate an endothermic signal around 177°C. NMR (Figure 29) results indicate shifts in peaks at 1.50-1.90 ppm, 2.98 ppm, 3.07 ppm, 4.11 ppm, 6.90 ppm, and 7.08 ppm compared to the free form, suggesting salt formation. A succinic acid peak is observed at 2.39 ppm, indicating a 1:1 API to succinic acid ratio based on integration. A solvent peak for methyl tert-butyl ether is observed at 1.10 ppm, suggesting the presence of a small amount of residual methyl tert-butyl ether solvent. In summary, Form J succinate salt is an anhydrous form.

[0376] Example 13 Preparation of Glycolate Form K

[0377] 25.9 mg of the compound represented by formula (I) was added with 1.0 mL of methyl tert-butyl ether and 1 equivalent of glycolic acid. The mixture was stirred at room temperature for 2 days and centrifuged to obtain glycolate crystal form K.

[0378] XRPD (Figure 30) results show that glycolate salt form K is a well-crystalline solid. TGA (Figure 31) results show that the sample loses 0.7% weight during heating to 70°C and continues to lose weight during subsequent heating, and may decompose after 150°C. DSC results show an endothermic signal at around 98°C. NMR (Figure 32) results show that compared with the free state, the peaks at 2.98ppm, 3.07ppm, 4.11ppm, 6.90ppm, and 7.08ppm are shifted, suggesting that the sample has formed a salt; a signal peak for glycolic acid is visible at 3.87ppm; and a solvent peak for methyl tert-butyl ether is visible at 1.10ppm, suggesting that the sample contains a very small amount of methyl tert-butyl ether solvent. In summary, glycolate salt form K may be an anhydrate / hydrate.

[0379] Example 14 Preparation of Benzoic Acid Cocrystal Form L

[0380] 24.7 mg of the compound represented by formula (I) was added to 0.8 mL of isopropanol and 1 equivalent of benzoic acid. The mixture was stirred at room temperature for 2 days and centrifuged to obtain benzoic acid cocrystal Form L.

[0381] XRPD (Figure 33) results indicate that benzoic acid cocrystal Form L is a well-crystalline solid. TGA (Figure 34) results indicate a 1.6% weight loss upon heating to 100°C, with possible decomposition occurring after 135°C. DSC (Figure 34) results indicate endothermic signals at approximately 165°C and 177°C. NMR (Figure 35) results indicate no peak shift compared to the free form, suggesting that the sample has not formed a salt and may instead form a cocrystal. Benzoic acid signal peaks are visible between 7.0 and 8.5 ppm, indicating a 1:1 API to benzoic acid ratio based on integration. An isopropanol solvent peak is visible at 1.04 ppm, suggesting the presence of a small amount of residual isopropanol solvent. In summary, benzoic acid cocrystal Form L is an anhydrous form.

[0382] Example 15 Preparation of Benzoic Acid Cocrystal Form M

[0383] 25.2 mg of the compound represented by formula (I) was added to 1.0 mL of cyclohexane and 1 equivalent of benzoic acid. The mixture was stirred at room temperature for 2 days and centrifuged to obtain benzoic acid cocrystal Form M.

[0384] XRPD (Figure 36) results indicate that benzoic acid cocrystal Form M is a poorly crystalline solid. TGA (Figure 37) results indicate a 1.0% weight loss upon heating to 100°C, with possible decomposition occurring after 135°C. DSC (Figure 37) results indicate an endothermic signal at approximately 175°C. NMR (Figure 38) results indicate no peak shift compared to the free form, suggesting that the sample has not formed a salt and may instead form a cocrystal. Benzoic acid signal peaks are visible at 7.0-8.5 ppm, indicating a 1:1 ratio of raw material to benzoic acid based on integration. A cyclohexane solvent peak is visible at 1.39 ppm, suggesting a small amount of residual cyclohexane solvent. In summary, benzoic acid cocrystal Form M is an anhydrous form.

[0385] Example 16 Preparation of Form N

[0386] 20.4 mg of the compound represented by formula (I) was added to 0.5 mL of toluene, suspended and stirred at 50° C. for one day, and centrifuged to obtain Form N.

[0387] XRPD (Figure 39) results indicate that Form N is a well-crystalline solid. TGA (Figure 40) results indicate that Form N loses 0.6% weight upon heating to 150°C, and decomposition may occur above 300°C. DSC (Figure 40) results indicate a melting endotherm at approximately 208°C. NMR (Figure 41) results indicate a toluene solvent peak at 2.30 ppm, suggesting that this sample contains a small amount of residual toluene solvent. In summary, Form N is an anhydrous crystalline form.

[0388] Example 17 Preparation of Form O

[0389] 19.5 mg of the compound represented by formula (I) was dissolved in 0.6 mL of ethanol, 9.0 mL of n-heptane was slowly added, the mixture was suspended and stirred for 15 minutes, and then centrifuged to obtain Form O.

[0390] XRPD (Figure 42) results indicate that Form O is a well-crystalline solid. TGA (Figure 43) results indicate that Form O loses 2.6% weight upon heating to 200°C, and decomposition may occur above 300°C. DSC (Figure 43) results indicate that Form O has an exothermic peak around 196°C, an endothermic signal around 190°C, and a melting endothermic peak around 208°C. Thermal crystallization experiments indicate that Form O recrystallizes into Form N after desolvation. NMR (Figure 44) results indicate that this sample exhibits an ethanol solvent peak at 1.06 ppm. Based on the integrated results, the compound-to-ethanol ratio is 1:0.25, which is consistent with the TGA weight loss (theoretical weight loss of 2.2%). In summary, Form O is either an ethanol / n-propanol solvate or an anhydrous form of ethanol / n-propanol encapsulated within the crystals.

[0391] Example 18 Preparation of Form P

[0392] 20.9 mg of the compound represented by formula (I) was dissolved in 1.4 mL of acetonitrile and 1.0 mL of water. The solution was allowed to stand at room temperature for evaporation until the solvent was completely evaporated, and then centrifuged to obtain Form P.

[0393] XRPD (Figure 45) results show that Form P is a well-crystalline solid with a distinct preferred orientation. TGA (Figure 46) results show that Form P loses 3.3% weight upon heating to 175°C, and decomposition may occur above 300°C. DSC (Figure 46) results show that Form P has an exothermic peak around 158°C, an endothermic signal around 145°C, and a melting endothermic peak around 211°C. Thermal crystallization experiments indicate that Form P recrystallizes to Form N after desolvation. NMR (Figure 47) results show that this sample has no obvious organic solvent peaks. In summary, Form P is a hydrate.

[0394] Example 19 Preparation of Form Q

[0395] 19.9 mg of the compound represented by formula (I) was dissolved in 4.5 mL of diethyl ether and allowed to stand open at room temperature until the solvent was completely evaporated to obtain Form Q.

[0396] XRPD (Figure 48) results show that Form Q is a well-crystalline solid. TGA (Figure 49) results show that Form Q loses 4.6% weight upon heating to 180°C, and decomposition may occur above 300°C. DSC (Figure 49) results show that Form Q has an exothermic peak around 181°C, endothermic signals around 171°C and 198°C, and a melting endothermic peak around 207°C. Thermal crystallization experiments indicate that Form Q recrystallizes into Form N after desolvation.

[0397] Example 20 Preparation of Form R

[0398] 19.9 mg of the compound represented by formula (I) was added dropwise with 0.8 mL of acetonitrile at room temperature until completely dissolved, and then 3.0 mL of water was added dropwise until solid precipitated. After suspending at room temperature for 15 minutes, the system was centrifuged and dried under vacuum at room temperature to obtain Form R.

[0399] XRPD (Figure 50) results indicate that Form R is a well-crystalline solid. TGA (Figure 51) results indicate that Form R loses 3.7% weight upon heating to 150°C, and decomposition may occur above 300°C. DSC (Figure 51) results indicate that Form R has an exothermic peak around 161°C, an endothermic signal around 154°C, and a melting endothermic peak around 211°C. Thermal crystallization experiments indicate that Form R recrystallizes to Form N after desolvation. NMR (Figure 52) results indicate the absence of significant organic solvent peaks. In summary, Form R is a hydrate.

[0400] Example 21 Preparation of Form S

[0401] 400.0 mg of the compound of formula (I) was placed in a glass vial, 10.5 mL of a 1 / 6, v / v, isopropanol / water mixture was added, and the mixture was suspended at 50°C for 1 day. The resulting solid was centrifuged and dried in vacuo at 40°C for 1 day to obtain Form S.

[0402] XRPD (Figure 53) results show that Form S is a well-crystalline solid. TGA (Figure 54) results show that Form S loses 3.6% weight upon heating to 150°C, and decomposition may occur above 300°C. DSC (Figure 54) results show that Form S has an exothermic peak around 155°C, an endothermic signal around 126°C, and a melting endothermic peak around 210°C. Thermal crystallization experiments indicate that Form S recrystallizes to Form N after desolvation. In summary, Form S is a hydrate. NMR is shown in Figure 55.

[0403] Example 22 Preparation of Form T

[0404] 20.4 mg of the compound represented by formula (I) was dissolved in 0.1 mL of dichloromethane and evaporated to dryness at room temperature to obtain Form T.

[0405] XRPD (Figure 56) results indicate that Form T is a well-crystalline solid. TGA (Figure 57) results indicate a 6.7% weight loss upon heating to 200°C, with possible decomposition occurring above 300°C. DSC (Figure 57) results indicate an exothermic peak around 191°C, an endothermic signal around 186°C, and a melting endothermic peak around 209°C. NMR (Figure 58) results indicate no structural changes, with solvent peaks for dichloromethane and a small amount of dioxane visible at 5.76ppm and 3.57ppm, respectively. Based on the integration results, the compound-to-dichloromethane ratio is calculated to be 1:0.25. In summary, Form T is either a dichloromethane solvate or an anhydrous dichloromethane occluded within the crystals.

[0406] Example 23 Preparation of Form U

[0407] 23.5 mg of the compound represented by formula (I) was added to 1.0 mL of cyclohexane and 1 equivalent of propionic acid. The mixture was stirred at room temperature for 2 days. The suspension was centrifuged and the solid was dried under vacuum at room temperature to obtain Form U.

[0408] XRPD (Figure 59) results showed that it was a well-crystalline solid. TGA (Figure 60) results showed that the sample lost 18.0% of its weight during heating to 130°C, corresponding to the weight loss of approximately 2 propionic acid molecules. DSC (Figure 60) results showed endothermic signals at around 109°C, 121°C, and 204°C. NMR (Figure 61) results showed that no peak shifted compared to the free state, suggesting that the sample was not salted; propionic acid signal peaks were visible at 0.99ppm and 2.20ppm. According to the integration results, the ratio of API to propionic acid was 1:2; a cyclohexane solvent peak was visible at 1.39ppm, suggesting that a small amount of cyclohexane solvent remained in the sample. In summary, Form U is a propionic acid solvate.

[0409] Example 24 Stability Study

[0410] Stability studies were conducted on the maleate salt Form A, fumarate salt Form C, Form N, and Form S under conditions of high temperature (60°C), high humidity (25°C / 92.5% RH), light (25°C / 4500 Lux), and accelerated exposure (40°C / 75% RH). Samples were taken for XRPD characterization after 7 days and 15 days, respectively. The results are shown in Table 28 and Figures 62-65. The XRPD results showed that the maleate salt Form A and the fumarate salt Form C were stable under the conditions of high temperature, high humidity, light, and accelerated exposure for 15 days, with no polymorphic transformation occurring.

[0411] Table 28

[0412] Example 25 Biological Media Solubility Test

[0413] Dynamic solubility assays were performed in three biological media (FaSSIF, FeSSIF, and FaSSGF), and the results are shown in Table 29 below and Figures 66 and 67.

[0414] Table 29

[0415] *The sample was first dissolved in FaSSGF and then shaken for 24 hours to precipitate an amorphous solid.

[0416] In the description of this specification, the reference terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and features of different embodiments or examples without contradiction.

[0417] Although the embodiments of the present invention have been shown and described above, it will be understood that the above embodiments are illustrative and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention.

Claims

1. A maleate salt of a compound represented by formula (I), whose structure is represented by formula (II), 2. Maleate salt form A of the compound represented by formula (I), wherein: The X-ray powder diffraction pattern of the crystalline form A has characteristic diffraction peaks at the following 2θ angles: 9.14±0.2°, 12.88±0.2°, 18.31±0.2°, 18.90±0.2°, 20.60±0.2°, and 27.61±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form A has characteristic diffraction peaks at the following 2θ angles: 9.14±0.2°, 12.88±0.2°, 17.19±0.2°, 18.31±0.2°, 18.90±0.2°, 20.60±0.2°, 21.45±0.2°, 27.61±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form A has characteristic diffraction peaks at the following 2θ angles: 9.14±0.2°, 12.88±0.2°, 17.19±0.2°, 18.31±0.2°, 18.90±0.2°, 19.70±0.2°, 20.20±0.2°, 20.60±0.2°, 21.45±0.2°, 21.91±0.2°, 27.61±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form A has characteristic diffraction peaks at the following 2θ angles: 9.14±0.2°, 12.88±0.2°, 17.19±0.2°, 18.31±0.2°, 18.90±0.2°, 19.70±0.2°, 20.20±0.2°, 20.60±0.2°, 21.45±0.2°, 21.91±0.2°, 25.96±0.2°, 26.53±0.2°, 27.61±0.2°, 29.22±0.2°, 30.20±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form A has an X-ray powder diffraction pattern substantially as shown in FIG1 .

3. Maleate salt form B of the compound represented by formula (I), wherein The X-ray powder diffraction pattern of the crystalline form B has characteristic diffraction peaks at the following 2θ angles: 8.97±0.2°, 15.73±0.2°, 18.31±0.2°, 20.15±0.2°, 21.12±0.2°, and 24.70±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form B has characteristic diffraction peaks at the following 2θ angles: 7.40±0.2°, 8.97±0.2°, 10.11±0.2°, 13.94±0.2°, 15.73±0.2°, 18.31±0.2°, 19.02±0.2°, 20.15±0.2°, 21.12±0.2°, 24.70±0.2°; Optionally, the X-ray powder diffraction pattern of Form B has an X-ray powder diffraction pattern substantially as shown in FIG6 .

4. A fumarate salt of the compound represented by formula (I), whose structure is represented by formula (III), 5. A fumarate salt of the compound represented by formula (I), Form C, wherein: The X-ray powder diffraction pattern of the crystalline form C has characteristic diffraction peaks at the following 2θ angles: 12.77±0.2°, 14.44±0.2°, 20.00±0.2°, 20.64±0.2°, 21.33±0.2°, and 21.87±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form C has characteristic diffraction peaks at the following 2θ angles: 12.77±0.2°, 13.17±0.2°, 14.44±0.2°, 17.18±0.2°, 20.00±0.2°, 20.64±0.2°, 21.33±0.2°, 21.87±0.2°, 23.43±0.2°, 25.86±0.2°; Optionally, the X-ray powder diffraction pattern of Form C has an X-ray powder diffraction pattern substantially as shown in FIG9 .

6. A hydrochloride of the compound represented by formula (I), whose structure is represented by formula (IV), 7. The hydrochloride crystal form D of the compound represented by formula (I), wherein The X-ray powder diffraction pattern of the crystalline form D has characteristic diffraction peaks at the following 2θ angles: 8.13±0.2°, 9.27±0.2°, 9.91±0.2°, 13.53±0.2°, 16.37±0.2°, and 17.09±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form D has characteristic diffraction peaks at the following 2θ angles: 8.13±0.2°, 9.27±0.2°, 9.91±0.2°, 12.86±0.2°, 13.53±0.2°, 16.37±0.2°, 17.09±0.2°, 18.67±0.2°, 21.77±0.2°, 23.81±0.2°; Optionally, the X-ray powder diffraction pattern of Form D has an X-ray powder diffraction pattern substantially as shown in FIG12 .

8. The hydrochloride crystalline form E of the compound represented by formula (I), wherein The X-ray powder diffraction pattern of the crystalline form E has characteristic diffraction peaks at the following 2θ angles: 3.86±0.2°, 13.60±0.2°, 14.19±0.2°, 18.06±0.2°, 20.50±0.2°, and 21.24±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form E has characteristic diffraction peaks at the following 2θ angles: 3.86±0.2°, 6.74±0.2°, 11.73±0.2°, 13.60±0.2°, 14.19±0.2°, 18.06±0.2°, 20.50±0.2°, 21.24±0.2°, 23.72±0.2°, 24.06±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form E has an X-ray powder diffraction pattern substantially as shown in FIG15 .

9. The hydrochloride crystalline form F of the compound represented by formula (I), wherein The X-ray powder diffraction pattern of the crystalline form F has characteristic diffraction peaks at the following 2θ angles: 5.84±0.2°, 11.77±0.2°, 13.29±0.2°, 17.82±0.2°, 20.49±0.2°, and 20.94±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form F has characteristic diffraction peaks at the following 2θ angles: 5.84±0.2°, 11.77±0.2°, 13.29±0.2°, 14.34±0.2°, 17.82±0.2°, 18.67±0.2°, 20.49±0.2°, 20.94±0.2°, 23.02±0.2°, 23.68±0.2°; Optionally, the X-ray powder diffraction pattern of Form F has an X-ray powder diffraction pattern substantially as shown in FIG18 .

10. A sulfate of the compound represented by formula (I), whose structure is represented by formula (V), 11. The sulfate crystal form G of the compound represented by formula (I), wherein The X-ray powder diffraction pattern of the crystalline form G has characteristic diffraction peaks at the following 2θ angles: 10.30±0.2°, 13.02±0.2°, 16.60±0.2°, 18.53±0.2°, 20.67±0.2°, and 22.26±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form G has characteristic diffraction peaks at the following 2θ angles: 6.46±0.2°, 10.30±0.2°, 13.02±0.2°, 16.60±0.2°, 17.66±0.2°, 18.53±0.2°, 19.98±0.2°, 20.67±0.2°, 22.26±0.2°, 23.62±0.2°; Optionally, the X-ray powder diffraction pattern of Form G has an X-ray powder diffraction pattern substantially as shown in Figure 21.

12. A succinate salt of the compound represented by formula (I), wherein the structure is represented by formula (VI):

13. A succinate salt of the compound represented by formula (I) in form H, wherein: The X-ray powder diffraction pattern of the crystalline form H has characteristic diffraction peaks at the following 2θ angles: 10.30±0.2°, 14.63±0.2°, 18.59±0.2°, 20.13±0.2°, 21.83±0.2°, and 22.30±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form H has characteristic diffraction peaks at the following 2θ angles: 10.30±0.2°, 12.91±0.2°, 14.63±0.2°, 18.59±0.2°, 19.41±0.2°, 20.13±0.2°, 20.69±0.2°, 21.83±0.2°, 22.30±0.2°, 23.65±0.2°; Optionally, the X-ray powder diffraction pattern of Form H has an X-ray powder diffraction pattern substantially as shown in FIG. 24 .

14. The succinate salt of the compound represented by formula (I) in Form J, wherein: The X-ray powder diffraction pattern of the crystalline form J has characteristic diffraction peaks at the following 2θ angles: 9.61±0.2°, 11.56±0.2°, 12.93±0.2°, 17.12±0.2°, 17.71±0.2°, and 19.95±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form J has characteristic diffraction peaks at the following 2θ angles: 9.61±0.2°, 11.56±0.2°, 12.93±0.2°, 13.76±0.2°, 17.12±0.2°, 17.71±0.2°, 19.51±0.2°, 19.95±0.2°, 21.83±0.2°, 22.42±0.2°; Optionally, the X-ray powder diffraction pattern of Form J has an X-ray powder diffraction pattern substantially as shown in FIG. 27 .

15. A glycolate salt of the compound represented by formula (I), wherein the structure thereof is represented by formula (VII), 16. A glycolate crystalline form K of the compound represented by formula (I), wherein: The X-ray powder diffraction pattern of the crystal form K has characteristic diffraction peaks at the following 2θ angles: 12.51±0.2°, 15.99±0.2°, 18.71±0.2°, 20.18±0.2°, 20.59±0.2°, and 21.64±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form K has characteristic diffraction peaks at the following 2θ angles: 12.51±0.2°, 13.62±0.2°, 15.99±0.2°, 16.65±0.2°, 18.71±0.2°, 20.18±0.2°, 20.59±0.2°, 21.64±0.2°, 22.62±0.2°, 24.53±0.2°; Optionally, the X-ray powder diffraction pattern of Form K has an X-ray powder diffraction pattern substantially as shown in FIG30 .

17. A benzoate salt of the compound represented by formula (I), wherein the structure thereof is represented by formula (VIII), 18. Benzoic acid cocrystal Form M of the compound represented by formula (I), wherein: The X-ray powder diffraction pattern of the crystalline form M has characteristic diffraction peaks at the following 2θ angles: 9.31±0.2°, 13.77±0.2°, 14.54±0.2°, 19.84±0.2°, 20.34±0.2°, and 21.70±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form M has characteristic diffraction peaks at the following 2θ angles: 9.31±0.2°, 13.77±0.2°, 14.54±0.2°、16.55±0.2°、17.66±0.2°、18.68±0.2°、19.84±0.2°、20.34±0.2°、21.70±0.2°、23.32±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form M has an X-ray powder diffraction pattern substantially as shown in Figure 36.

19. Crystalline Form N of the compound represented by formula (I), wherein The X-ray powder diffraction pattern of the crystalline form N has characteristic diffraction peaks at the following 2θ angles: 10.38±0.2°, 13.54±0.2°, 14.41±0.2°, 16.32±0.2°, 18.10±0.2°, and 19.05±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form N has characteristic diffraction peaks at the following 2θ angles: 10.38±0.2°, 13.54±0.2°, 14.41±0.2°, 15.90±0.2°, 16.32±0.2°, 18.10±0.2°, 19.05±0.2°, 22.14±0.2°, 22.91±0.2°, 23.66±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form N has an X-ray powder diffraction pattern substantially as shown in Figure 39.

20. Crystalline Form O of the compound represented by formula (I), wherein The X-ray powder diffraction pattern of the crystalline form O has characteristic diffraction peaks at the following 2θ angles: 4.75±0.2°, 9.65±0.2°, 15.70±0.2°, 16.88±0.2°, 18.00±0.2°, and 18.97±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form O has characteristic diffraction peaks at the following 2θ angles: 4.75±0.2°, 9.65±0.2°, 15.70±0.2°, 16.88±0.2°, 18.00±0.2°, 18.97±0.2°, 19.89±0.2°, 21.86±0.2°, 22.67±0.2°, 24.30±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form O has an X-ray powder diffraction pattern substantially as shown in Figure 42.

21. The crystalline form P of the compound represented by formula (I), wherein The X-ray powder diffraction pattern of the crystalline form P has characteristic diffraction peaks at the following 2θ angles: 13.07±0.2°, 17.98±0.2°, 21.64±0.2°, 23.78±0.2°, 26.36±0.2°, and 33.13±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form P has an X-ray powder diffraction pattern substantially as shown in Figure 45.

22. Crystalline Form Q of the compound represented by formula (I), wherein The X-ray powder diffraction pattern of the crystalline form Q has characteristic diffraction peaks at the following 2θ angles: 3.48±0.2°, 10.60±0.2°, 12.32±0.2°, 15.41±0.2°, 16.60±0.2°, and 17.09±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form Q has characteristic diffraction peaks at the following 2θ angles: 3.48±0.2°, 10.60±0.2°, 12.32±0.2°, 15.41±0.2°, 16.60±0.2°, 17.09±0.2°, 17.75±0.2°, 18.79±0.2°, 20.49±0.2°, 21.40±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form Q has an X-ray powder diffraction pattern substantially as shown in Figure 48.

23. The crystalline form R of the compound represented by formula (I), wherein The X-ray powder diffraction pattern of the crystalline form R has characteristic diffraction peaks at the following 2θ angles: 6.70±0.2°, 13.30±0.2°, 18.15±0.2°, 21.39±0.2°, 22.97±0.2°, and 26.71±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form R has an X-ray powder diffraction pattern substantially as shown in Figure 50.

24. Crystalline Form S of the compound represented by formula (I), wherein The X-ray powder diffraction pattern of the crystalline form S has characteristic diffraction peaks at the following 2θ angles: 14.97±0.2°, 15.34±0.2°, 17.97±0.2°, 22.81±0.2°, 23.54±0.2°, and 24.69±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline Form S has an X-ray powder diffraction pattern substantially as shown in Figure 53.

25. Crystalline Form T of the compound represented by formula (I), wherein The X-ray powder diffraction pattern of the crystalline form T has characteristic diffraction peaks at the following 2θ angles: 15.84±0.2°, 17.03±0.2°, 17.60±0.2°, 20.01±0.2°, 22.22±0.2°, and 22.82±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form T has characteristic diffraction peaks at the following 2θ angles: 13.64±0.2°, 14.70±0.2°, 15.84±0.2°, 17.03±0.2°, 17.60±0.2°, 19.01±0.2°, 20.01±0.2°, 22.22±0.2°, 22.82±0.2°, 24.45±0.2°; Optionally, the X-ray powder diffraction pattern of Form T has an X-ray powder diffraction pattern substantially as shown in Figure 56.

26. Crystalline Form U of the compound represented by formula (I), wherein The X-ray powder diffraction pattern of the crystalline form U has characteristic diffraction peaks at the following 2θ angles: 8.01±0.2°, 9.27±0.2°, 12.68±0.2°, 16.15±0.2°, 17.94±0.2°, and 19.31±0.2°; Optionally, the X-ray powder diffraction pattern of the crystalline form U has characteristic diffraction peaks at the following 2θ angles: 8.01±0.2°, 9.27±0.2°, 12.68±0.2°, 16.15±0.2°, 17.94±0.2°, 19.31±0.2°, 22.16±0.2°, 22.82±0.2°, 23.80±0.2°, 24.08±0.2°; Optionally, the X-ray powder diffraction pattern of Form U has an X-ray powder diffraction pattern substantially as shown in Figure 59.

Citation Information

Patent Citations

  • Benzoheterocyclic compounds

    CN1051038A

  • Tricyclic benzazepine vasopressin antagonists

    US5869483A

  • Novel benzazepine spiro derivative

    WO2022111581A1

  • New-type benzazepine fused ring derivative

    WO2022184172A1